Composition, adsorption and storage device containing same and associated gas recovery system

By using multi-level Pole MOFS base compound phase change materials and medium pressure-low temperature-phase change temperature control technology, the problem of low-qi recovery efficiency of the oilfield single-lapse wells is solved, and the efficient recycling and low of the vitality of the small gas volume is low. Cost recycling.

CN119327416AActive Publication Date: 2025-01-21CHINA PETROLEUM & CHEMICAL CORP +2

Patent Information

Application Number
CN202310886204.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-19
Publication Date
2025-01-21
Estimated Expiration
2043-07-19

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently recover single-pull well-accompanied gas in oilfields, especially small gas volumes and scattered gas, and traditional adsorption technology has the problem of thermal adsorption effect.

Method used

The multi-level pore MOFS base composite phase variable material is used as the adsorbent, and the efficient recovery of the volume of the small gas volume through the medium pressure-low temperature-phase change temperature control process is achieved. The material includes a multi -level hole structure of micro -pores, metors, and large holes, and the load phase changes material to control the adsorption heat.

Benefits of technology

The efficient recycling of the vaporous scattered companionship is realized, the adsorption temperature rise is reduced, the adsorption capacity is increased, the process cost is low, and it is suitable for the application of remote wells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119327416A_ABST
    Figure CN119327416A_ABST
Patent Text Reader

Abstract

The invention provides a composition, an adsorption and storage device containing the composition and an associated gas recovery system. The composition comprises a hierarchical porous MOFs-based composite phase change material and an adsorption material, and the adsorption storage device is an adsorption storage tank with the composition as bed filling. The associated gas recovery system mainly comprises a pressurizing unit, a cooling, condensing and dehumidifying unit and an adsorption and storage unit, wherein the adsorption and storage unit is the adsorption and storage device. The associated gas recovery system can realize a medium pressure-low temperature-phase change temperature control-adsorption storage single pull well associated gas recovery process, and realizes efficient recovery of single pull well associated gas with small gas volume, low casing pressure and far distance from a gathering and transportation station at low cost at low pressure (specifically 2-4MPa).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of associated gas recovery, and in particular relates to a composition, an adsorption storage device containing the composition, and an associated gas recovery system. Background Art

[0002] Oilfield associated gas is usually rich in methane and other low molecular weight alkane gas mixtures. During crude oil production, a large amount of oilfield associated gas is vented or burned, which not only causes energy waste, but also causes environmental pollution and aggravation of the greenhouse effect. Therefore, recycling associated gas can achieve the triple benefits of carbon emission reduction, reducing volatile organic compounds (VOCs) and pollution reduction, and recycling resources. Especially in the current response to global climate change and the development of a low-carbon economy, its significance is particularly prominent.

[0003] The oil pipe connection technology is the most commonly used associated gas recovery technology in oil fields. It can realize the automatic recovery of casing gas with casing pressure greater than back pressure. The technology is easy to install and has a simple structure. This technology requires the use of crude oil gathering pipelines, and it is difficult to recover associated gas with casing pressure less than back pressure. In addition, the check valve is prone to freezing in winter, so the application scope of this technology is greatly limited and it is difficult to promote and apply it in remote wells.

[0004] In addition to process wells, there are also a large number of single-pull wells in the oil field. The gas volume of associated gas in such wells is unstable, the location is scattered, and it is far away from the pipeline system. Due to the lack of efficient and economical recovery technology, it has not been developed and utilized for a long time, resulting in great waste of resources and environmental pollution. For example, the combustion of associated gas is also a very common way of recycling. The recovered associated gas can be used for heating water jacket furnaces, heating multi-functional tanks of oil wells, and heating duty rooms and injection and production stations, which can save electricity. However, there is a common problem of substandard emissions in the combustion process, which causes environmental pollution. Due to the large differences in basic parameters such as pressure, output, and stable production period of scattered associated gas, especially the recovery method of small-volume scattered associated gas is still in the exploratory stage, and no widely applicable, economical and efficient recovery technology has been promoted and applied.

[0005] Compared with compressed natural gas (CNG) technology, adsorbed natural gas (ANG) technology has a lower storage pressure and is safe, flexible and convenient. ANG can be flexibly designed according to resource and regional characteristics to improve the utilization efficiency of natural gas, so ANG with superior performance has strong economic advantages and market competitiveness. With the deepening of ANG technology research, certain results have been achieved in adsorbent research and development, storage tank design, and thermal effect suppression. Studies have shown that ANG recovery technology can use microporous adsorbent materials to adsorb methane molecules at room temperature and medium pressure (3-5MPa). The storage pressure of ANG at room temperature is only 1 / 5 of that of CNG, and the storage and transportation capacity of the two are comparable. In addition, the investment and operating costs of ANG are 48% lower than those of CNG. The tank material and shape are highly selective, the safety factor is high, and it has good economy and safety. However, the adsorption heat effect of the adsorbent restricts the development of ANG technology: during the gasification process, methane molecules are adsorbed on the surface of the adsorbent, and their kinetic energy is converted into heat energy, which causes the adsorbent temperature to rise and the methane adsorption amount to decrease; during the gas release, methane molecules need to absorb energy during the desorption process, which reduces the adsorbent temperature, resulting in a decrease in desorption and an increase in cushion gas. Therefore, it is urgent to develop a single-pull well small-volume scattered associated gas recovery technology with a wide range of applications and economical and efficient. Summary of the invention

[0006] In view of the above problems, the purpose of the present invention is to provide an associated gas recovery system to realize an associated gas recovery process of medium pressure-low temperature-phase change temperature control-adsorption storage, so as to achieve efficient recovery of associated gas from single-pull wells with small gas volume, low casing pressure and long distance from gathering and transportation stations at a lower pressure (specifically 2-4MPa) at low cost.

[0007] To achieve the above-mentioned objectives, the first aspect of the present invention provides a multi-level porous MOFs (i.e., metal organic framework compound) based composite phase change material, the second aspect of the present invention provides a method for preparing a multi-level porous MOFs based composite phase change material, the third aspect of the present invention provides an application of a multi-level porous MOFs based composite phase change material in the adsorption of VOCs, the fourth aspect of the present invention provides a composition, the fifth aspect of the present invention provides an adsorption storage device, the sixth aspect of the present invention provides an associated gas recovery system, and the seventh aspect of the present invention provides an associated gas recovery process.

[0008] Specifically, the first aspect of the present invention provides a multi-level porous MOFs-based composite phase change material, which includes a multi-level porous MOFs material having micropores, mesopores and macropores, and a phase change material loaded in the macropore channels of the multi-level porous MOFs material.

[0009] Preferably, the ratio of the micropore volume, mesopore volume and macropore volume of the hierarchical porous MOFs material is 1-4:1-2:1.

[0010] Preferably, the specific surface area of ​​the multi-level porous MOFs material is 600-1700m 2 / g.

[0011] Preferably, the phase change material is selected from one or more of polyols, fatty acids, linear alkanes and paraffins.

[0012] Preferably, the polyols are polyethylene glycol and / or neopentyl glycol.

[0013] Preferably, the fatty acid is selected from one or more of lauric acid, stearic acid, palmitic acid and pentadecanoic acid.

[0014] Preferably, the straight-chain alkane is selected from one or more of n-tetradecane, n-hexadecane and n-octadecane.

[0015] The second aspect of the present invention provides a method for preparing the above-mentioned multi-level porous MOFs-based composite phase change material, the preparation method comprising the following steps:

[0016] (1) mixing a first metal salt with water to obtain a first metal salt solution;

[0017] (2) mixing a template, a first organic ligand and a first organic solvent to obtain a first organic phase solution;

[0018] (3) mixing the first metal salt solution with the first organic phase solution, and then performing a first reaction, separating the solid and the liquid after the reaction, and washing and activating the obtained solid in sequence to obtain a hierarchical MOFs material;

[0019] (4) Mixing the phase change material with a first organic solvent to obtain an organic phase change material solution, and immersing the multi-level porous MOFs material in the organic phase change material solution.

[0020] Preferably, the first metal salt is selected from one or more of aluminum chloride hexahydrate, copper acetate monohydrate, chromium nitrate nonahydrate, zinc nitrate hexahydrate, zirconium chloride and nickel chloride hexahydrate.

[0021] Preferably, the content of the first metal salt in the first metal salt solution is 5-50 g / L.

[0022] Preferably, the template agent is selected from one or more of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, hexadecyltrimethylammonium bromide, sodium dodecylbenzenesulfonate and N,N,N,N-tetramethylethylenediamine.

[0023] Preferably, the first organic ligand is selected from one or more of 2-methylterephthalic acid, 2-aminoterephthalic acid, 2-nitroterephthalic acid, 2-sulfonateterephthalic acid, 2,3-dihydroxyterephthalic acid, terephthalic acid, phthalic acid, trimesic acid, 2,5-thiophenedicarboxylic acid and triethylenediamine.

[0024] Preferably, the first organic ligand is selected from one or more of 2-aminoterephthalic acid, 2,5-thiophenedicarboxylic acid, trimesic acid, terephthalic acid and triethylenediamine.

[0025] Preferably, the first organic solvent is selected from one or more of methanol, ethanol, N,N-dimethylformamide, dichloromethane and 1,2-dichloroethane.

[0026] Preferably, the content of the template in the first organic phase solution is 10-80 g / L, and the content of the first organic ligand is 30-150 g / L.

[0027] Preferably, the molar ratio of the first metal salt, the template and the first organic ligand is 1:0.03-1:1-2.

[0028] Preferably, in step (3), the conditions of the first reaction include: temperature of 20-160° C. and time of 6-18 h.

[0029] Preferably, the conditions of the first reaction include: temperature of 40-110° C. and time of 8-16 h.

[0030] Preferably, in step (3), the activation conditions include: temperature of 80-180° C., time of 1-24 h, and absolute vacuum of 20-80 kPa.

[0031] Preferably, the activation conditions include: temperature of 100-160° C. and time of 2-6 h.

[0032] Preferably, in step (4), the content of phase change material in the organic phase change material solution is 5-80 g / L.

[0033] Preferably, the weight ratio of the multi-level porous MOFs material to the organic phase change material is 1:0.05-0.5.

[0034] Preferably, in step (4), the immersion conditions include: time of 4-7 hours and temperature of 40-70°C.

[0035] A third aspect of the present invention provides an application of the above-mentioned multi-level porous MOFs-based composite phase change material in the adsorption of VOCs.

[0036] A fourth aspect of the present invention provides a composition comprising a multi-level porous MOFs-based composite phase change material and an adsorption material.

[0037] According to a specific embodiment of the present invention, the porous MOFs-based composite phase change material is the porous MOFs-based composite phase change material described in the first aspect of the present invention or the porous MOFs-based composite phase change material prepared by the method described in the second aspect of the present invention.

[0038] According to a specific embodiment of the present invention, the adsorption material is activated carbon or microporous MOFs material.

[0039] According to a specific embodiment of the present invention, the mass ratio of the multi-level porous MOFs-based composite phase change material to the adsorption material is 2-4:1-6.

[0040] According to a specific embodiment of the present invention, the adsorption material is activated carbon;

[0041] Preferably, the mass ratio of the multi-level porous MOFs-based composite phase change material to the activated carbon is 3:1, 4:3 or 2:6;

[0042] Preferably, the specific surface area of ​​the activated carbon is 1000-1600m 2 / g; and / or

[0043] The total pore volume of the activated carbon is 0.4-1.0 mL / g; and / or the micropore volume in the total pore volume is 0.2-0.7 mL / g.

[0044] According to a specific embodiment of the present invention, the adsorption material is a microporous MOFs material;

[0045] Preferably, the mass ratio of the multi-level porous MOFs-based composite phase change material to the microporous MOFs material is 3:1, 4:3 or 2:6;

[0046] Preferably, the specific surface area of ​​the microporous MOFs material is 1000-1500m 2 / g; and / or

[0047] The total pore volume of the microporous MOFs material is 0.5-0.8 mL / g; and / or the micropore volume in the total pore volume is 0.4-0.7 mL / g.

[0048] According to a specific embodiment of the present invention, the microporous MOFs material is prepared by the following method:

[0049] a. mixing the second metal salt with water to obtain a second metal salt solution;

[0050] b. mixing a second organic ligand and a second organic solvent to obtain a second organic phase solution;

[0051] c. mixing the second metal salt solution with the second organic phase solution, and then performing a second reaction, separating the solid and the liquid after the reaction, and washing and activating the obtained solid in sequence to obtain a microporous MOFs material;

[0052] Preferably, the second metal salt is selected from one or more of aluminum chloride hexahydrate, copper acetate monohydrate, chromium nitrate nonahydrate, zinc nitrate hexahydrate, zirconium chloride and nickel chloride hexahydrate; and / or

[0053] The content of the second metal salt in the second metal salt solution is 5-50 g / L; and / or

[0054] The second organic ligand is selected from one or more of 2-methylterephthalic acid, 2-aminoterephthalic acid, 2-nitroterephthalic acid, 2-sulfonateterephthalic acid, 2,3-dihydroxyterephthalic acid, terephthalic acid, phthalic acid, trimesic acid, 2,5-thiophenedicarboxylic acid and triethylenediamine; and / or

[0055] The second organic solvent is selected from one or more of methanol, ethanol, N,N-dimethylformamide, dichloromethane and 1,2-dichloroethane; and / or

[0056] The content of the second organic ligand in the second organic phase solution is 30-150 g / L; and / or

[0057] The molar ratio of the second metal salt to the second organic ligand is 1:1-2;

[0058] Preferably, the second metal salt is copper acetate monohydrate and / or aluminum chloride hexahydrate; and / or

[0059] The content of the second metal salt in the second metal salt solution is 35-45 g / L; and / or

[0060] The second organic ligand is trimesic acid and / or 2,5-thiophenedicarboxylic acid; and / or

[0061] The second organic solvent is anhydrous ethanol and / or N,N-dimethylformamide; and / or

[0062] The content of the second organic ligand in the second organic phase solution is 32-58 g / L; and / or

[0063] The molar ratio of the second metal salt to the second organic ligand is 1:1.29-1.58;

[0064] Preferably, in step c, the conditions of the second reaction include: temperature of 20-160° C., time of 6-18 h; and / or

[0065] In step c, the activation conditions include: temperature of 80-180° C., time of 1-24 h, and absolute vacuum of 20-80 kPa;

[0066] Preferably, in step c, the conditions of the second reaction include: temperature of 40-100° C., time of 8-9 h; and / or

[0067] In step c, the activation conditions include: temperature of 100-120° C., time of 4-6 h, and absolute vacuum of 60 kPa.

[0068] A fifth aspect of the present invention provides an adsorption storage device, which includes an adsorption storage tank and a first bed layer and a second bed layer filled in the adsorption storage tank;

[0069] The first bed layer is the composition comprising the multi-level porous MOFs-based composite phase change material and activated carbon as described in the fourth aspect of the present invention;

[0070] The second bed layer is the composition comprising the multi-level porous MOFs-based composite phase change material and the microporous MOFs material as described in the fourth aspect of the present invention.

[0071] According to a specific embodiment of the present invention, the mass ratio of the first bed layer to the second bed layer is 1-3:2-7;

[0072] Preferably, the mass ratio of the first bed layer to the second bed layer is 2-3:2-5; and / or

[0073] An air intake pipe with holes is radially arranged in the adsorption storage tank;

[0074] Preferably, the mass ratio of the first bed layer to the second bed layer is 2:5 or 3:2.

[0075] According to a specific embodiment of the present invention, in the adsorption storage tank, the first bed layer and the second bed layer are filled in sequence from the proximal end to the distal end of the adsorption storage tank inlet.

[0076] According to a specific embodiment of the present invention, in the adsorption storage tank, the first bed layer is a cylinder coaxial with the adsorption storage tank, and the second bed layer is a circular cylinder coaxial with the adsorption storage tank;

[0077] Preferably, in a cross section perpendicular to the axial direction of the adsorption storage tank, the second bed layer wraps the first bed layer in an annular shape.

[0078] The adsorption storage device of the present invention is filled with a composition composed of the multi-level porous MOFs-based composite phase change material and the adsorption material as a bed layer, which can effectively absorb adsorption heat through phase change, reduce the bed temperature, and avoid the generation of high-temperature hot spots in the bed. In addition, the adsorption storage device only has an air intake pipe radially arranged in the adsorption storage tank, and no heat exchange tube is arranged separately. The saved space can be filled with more compositions, thereby increasing the adsorption capacity of the adsorption storage device. In addition, in actual use, the capacity specifications of the adsorption storage tank used can be determined according to the content of low molecular weight hydrocarbons such as methane and ethane in the target associated gas, and the total filling mass of the first bed layer and the second bed layer in the adsorption storage tank can be further determined.

[0079] A sixth aspect of the present invention provides an associated gas recovery system, which comprises a pressurizing unit, a cooling condensation dehumidification unit and an adsorption storage unit connected in sequence;

[0080] The boosting unit includes a compressor 3 and a gas-liquid separation tank 5 connected to the compressor, wherein the compressor is used to boost the associated gas to produce compressed condensate and compressed gas, and the gas-liquid separation tank is used to perform a gas-liquid separation on the compressed condensate and compressed gas;

[0081] The cooling, condensing and dehumidifying unit comprises a heat exchanger 7, a condensate discharge pipeline 19 and a condensate tank 9 connected in sequence, wherein the heat exchanger is used to cool, condense and dehumidify the compressed gas to produce dry cooling gas and condensed liquid; the condensate discharge pipeline and the condensate tank are used to perform secondary gas-liquid separation on the dry cooling gas and the condensed liquid;

[0082] The adsorption storage unit includes an adsorption storage device 16 for adsorption storage of the dry cooling gas;

[0083] The adsorption storage device is the adsorption storage device described in the fifth aspect of the present invention.

[0084] In the associated gas recovery system provided by the present invention, the number of the adsorption storage devices can be increased in the adsorption storage unit according to the gas volume, and each adsorption storage device is connected in parallel.

[0085] According to a specific embodiment of the present invention, the associated gas recovery system further includes a buffer tank 2 disposed between the associated gas inlet valve 1 and the compressor 3 .

[0086] In the secondary gas-liquid separation process of the present invention, it is considered that a small amount of dry cooling gas will enter the condensate tank along with the condensed liquid. In addition, the pressure drop in the condensate tank will also cause a small amount of butane and pentane in the condensed liquid to be converted from liquid to gas again to produce volatile gas. In order to prevent the volatile gas from entering the associated gas recovery system again, an adsorption removal unit is also provided in the associated gas recovery system.

[0087] According to a specific embodiment of the present invention, an adsorption removal unit is provided between the condensate tank 9 and the buffer tank 2; it is used to adsorb and remove the volatile gas in the condensate tank;

[0088] Preferably, the adsorption removal unit comprises an adsorption tank 11 connected to the outlet of the condensate tank 9 and a pressure relief pipeline 18 connecting the outlet of the adsorption tank and the inlet of the buffer tank; and / or the pressure relief pipeline is further provided with a pressure relief valve 12; when the adsorption tank reaches a set pressure, the pressure relief valve can be opened to allow the dry cooling gas to return to the buffer tank along the pressure relief pipeline;

[0089] Preferably, the adsorption tank 11 is filled with activated carbon;

[0090] Preferably, the specific surface area of ​​the activated carbon is 1000-1600m 2 / g; and / or

[0091] The total pore volume of the activated carbon is 0.4-1.0 mL / g; and / or the micropore volume in the total pore volume is 0.2-0.7 mL / g.

[0092] According to a specific embodiment of the present invention, in the booster unit, a compressor heat exchanger 4 is further connected in parallel between the compressor 3 and the gas-liquid separation tank 5; and / or

[0093] In the cooling, condensing and dehumidifying unit, a valve 8 is provided on the condensate discharge line 19 to limit the dry cooling gas from entering the condensate tank 9; and / or a valve 10 is provided between the outlet of the condensate tank 9 and the inlet of the adsorption tank 11 to prevent the volatile gas entering the adsorption tank from returning to the condensate tank; and / or

[0094] In the adsorption storage unit, a pressure limiting valve 17 is provided at one end of the adsorption storage device 16 away from the inlet, and when the pressure in the adsorption storage device exceeds the set pressure of the pressure limiting valve, the pressure is automatically released to avoid danger caused by excessive pressure in the adsorption storage device due to temperature increase;

[0095] and / or

[0096] A valve 15 and a valve 14 are provided in sequence near the inlet of the adsorption storage device 16; and / or

[0097] The valve 14 is used to switch the adsorption storage device; and / or

[0098] The valve 15 is used to manually release the pressure of the adsorption storage device;

[0099] Preferably, a valve 6 is provided between the gas-liquid separator 5 and the heat exchanger 7 to prevent the unpressurized associated gas from entering the cooling, condensing and dehumidifying unit in advance; and / or

[0100] A valve 13 is provided between the heat exchanger 7 and the adsorption storage unit for maintaining the pressure in the heat exchanger 7 .

[0101] A seventh aspect of the present invention provides an associated gas recovery process, which comprises the following steps:

[0102] Providing an associated gas recovery system according to a sixth aspect of the present invention;

[0103] 1) The associated gas enters the compressor 3 and is compressed and heated to obtain the compressed gas and compressed condensate, and the compressed condensate enters the gas-liquid separation tank 5 to achieve the primary gas-liquid separation;

[0104] 2) passing the compressed gas obtained in step 1) into the heat exchanger 7 for cooling, condensation and dehumidification to obtain the dry cooling gas and condensed liquid, and the condensed liquid is discharged into the condensate tank 9 via the condensate discharge line 19 to achieve the secondary gas-liquid separation;

[0105] 3) The dry cooling gas obtained in step 2) is introduced into the adsorption storage device 16 for adsorption storage.

[0106] According to a specific embodiment of the present invention, in step 1), the pressure of the compressed gas is 2-4 MPa and / or the temperature is 40-70° C.; and / or

[0107] In step 2), the temperature of the dry cooling gas is 0-5°C.

[0108] According to a specific embodiment of the present invention, the associated gas is single-well associated gas.

[0109] The single-pull well associated gas referred to in the present invention refers to the content of low molecular weight alkanes such as methane and ethane exceeding 90% VOL, with a maximum upper limit of 100% VOL, and also contains a small amount of propane, butane, pentane, etc. and water vapor other than hydrocarbons, generally between 15% RH and 100% RH, especially small gas volume (less than 500m 3 / d), associated gas with a high proportion of low molecular weight alkanes (methane + ethane content exceeding 90% VOL) ​​and a certain humidity (15% RH to 100% RH).

[0110] The application of any one of the composition described in the fourth aspect of the present invention, the adsorption storage device described in the fifth aspect of the present invention, the associated gas recovery system described in the sixth aspect of the present invention and the associated gas recovery process described in the seventh aspect of the present invention in the recovery of associated gas from a single well.

[0111] Using the associated gas recovery system described in the sixth aspect of the present invention (such as Fig.12 ), using the associated gas recovery process described in the seventh aspect of the present invention, the process of recovering the associated gas from the single well is as follows:

[0112] Step 1) The associated gas from the single-pull well enters the buffer tank 2 through the inlet valve 1, and the buffer tank is used to adjust the pressure fluctuation of the system to maintain the stability of the system operating conditions; then the associated gas from the single-pull well passes through the buffer tank to the compressor 3 with a set pressure of 2-4MPa, and the associated gas from the single-pull well is pressurized to 2-4MPa (absolute pressure) in cooperation with the compression heat exchanger 4. At this time, the temperature of the pressurized associated gas from the single-pull well is also increased to 40-70°C, and the water vapor and some macromolecular hydrocarbons therein are converted from gas to liquid due to the increase in pressure. The obtained compressed gas and compressed condensate are separated into a gas and liquid in the gas-liquid separation tank 5 connected to the compressor; in this way, part of the water vapor and part of the macromolecular hydrocarbons including butane, pentane, etc. in the associated gas from the single-pull well are removed, which is beneficial to reduce the influence of water vapor and macromolecular hydrocarbons on the adsorption capacity of low-molecular alkanes such as methane and ethane in the adsorption storage device in the subsequent adsorption storage unit;

[0113] Step 2) When the pressure in the compressor 3 reaches its set value, open the valve 6 to allow the compressed gas to enter the heat exchanger 7 with a set pressure of 2-4 MPa. At this point, the valve 13 is always in a closed state; as the compressed gas is filled and the pressure in the heat exchanger 7 reaches its set value, adjust the opening of the valve 13 to maintain the pressure in the heat exchanger at about 2-4 MPa; the compressed gas exchanges heat with the refrigerant of the heat exchanger and the temperature is reduced to 0-5°C (for example, about 2°C). During the cooling process, most of the water vapor and a small amount of large molecular hydrocarbons including butane, pentane, etc. in the compressed gas are liquefied to obtain condensed liquid, while low molecular alkanes such as methane and ethane are converted into dry cooling gas. The obtained condensed liquid flows through the condensate discharge pipeline 19 connected to the heat exchanger and enters the condensate tank 9 (where the condensed liquid is initially cooled) through the valve 8. The oil-water separation step is completed, and the secondary gas-liquid separation is completed; during the secondary gas-liquid separation process, a small amount of dry cooling gas will enter the condensate tank along with the condensed liquid. In addition, the pressure drop in the condensate tank will also cause a small amount of butane and pentane in the condensed liquid to be converted from liquid to gas to produce volatile gas; the dry cooling gas and the volatile gas enter the adsorption tank 11 filled with activated carbon through the valve 10, wherein the volatile gas is adsorbed and removed by the adsorption tank 11 to avoid entering the associated gas recovery system again, and the dry cooling gas flows through the pressure relief pipeline 18 and the pressure relief valve 12 into the buffer tank, and the single-pull well associated gas that continuously enters the buffer tank at the inlet valve 1 continues to enter the system for recovery; in this way, the influence of water vapor and macromolecular hydrocarbons including butane, pentane, etc. on the adsorption capacity of the adsorption storage device can be further reduced on the basis of step 1);

[0114] Step 3) The dry cooling gas obtained by the cooling, condensing and dehumidifying unit enters the adsorption storage device 16 through the valve 14 and the manual valve 15 for adsorption storage, and the pressure of the adsorption storage device is set to 2-5MPa (for example, 4MPa). When the pressure therein reaches the set value, it is switched to the parallel adsorption storage device through the valve 14; in addition, the pressure of the pressure limiting valve 17 of each adsorption storage device is set to 6-8MPa (for example, 6MPa). When the pressure in the adsorption storage device is higher than the set pressure of the pressure limiting valve 17, the pressure limiting valve 17 opens and automatically discharges to avoid danger caused by excessive internal pressure due to the increase in temperature in the adsorption storage device. When the adsorption storage device reaches its set pressure, the manual valve 15 is closed, and the gas is collected to the transfer station regularly (for example, every day) to desorb and release the gas in the adsorption storage device from the device: first, the manual valve 15 is opened for natural pressure relief, and the desorbed gas is allowed to slowly enter the recovery system of the transfer station by controlling the opening of the manual valve 15 to avoid excessive impact on the system; then, vacuum desorption is performed, and the vacuum pump is turned on to pump the adsorption storage device to reduce the relative pressure in the device to -90 to -60 kPa (for example, -90 kPa), and after maintaining for 10-60 minutes (for example, 30 minutes), the manual valve 15 is closed, and the desorption is completed; the adsorption storage device after desorption is transported back to the associated gas recovery system to continue the adsorption storage of dry cooling gas.

[0115] Beneficial effects of the present invention:

[0116] In view of the problem of the restriction of thermal effect of ANG adsorbent and the difficulty in recovering scattered associated gas with small amount of gas from a single well in the prior art, the present invention provides a composition, an adsorption storage device containing the composition and an associated gas recovery system. The composition includes a multi-level pore MOFs-based composite phase change material and an adsorption material, and has the functions of phase change temperature control and adsorption storage, wherein the multi-level pore MOFs-based composite phase change material and the adsorption material synergize to reduce the adsorption temperature rise, weaken the adsorption heat effect, and increase the adsorption capacity of the composition for methane and ethane. The adsorption storage device includes an adsorption storage tank and the composition filled in the adsorption storage tank as a bed layer. Since the adsorption temperature rise of the composition for low molecular weight alkanes such as methane and ethane is low and the adsorption capacity is high, only an air inlet pipe is arranged radially in the adsorption storage tank without a heat exchange pipe, which saves the internal space of the adsorption storage tank and can fill more compositions. Combined with the formula design of the bed layer in the adsorption storage device and the design of the filling method, the adsorption storage of low molecular weight alkanes such as methane and ethane with a lower adsorption temperature rise and a higher adsorption capacity is achieved. The associated gas recovery system provided by the present invention mainly includes a boosting unit, a cooling, condensing and dehumidifying unit and an adsorption storage unit, wherein the adsorption storage unit is an adsorption storage device provided by the present invention. After the associated gas enters the associated gas recovery system, the boosting unit generates compressed gas and compressed condensate to achieve primary gas-liquid separation; the cooling, condensing and dehumidifying unit cools, condenses and dehumidifies the compressed gas to obtain dry cooling gas and condensed liquid obtained by condensing water vapor and macromolecular hydrocarbons including butane, pentane, etc., to achieve secondary gas-liquid separation; the adsorption storage device in the adsorption storage unit adsorbs and stores the dry cooling gas. The primary gas-liquid separation removes part of the water vapor and macromolecular hydrocarbons in the associated gas, and the secondary gas-liquid separation further removes most of the water vapor and macromolecular hydrocarbons including butane, pentane, etc. in the associated gas on the basis of the primary gas-liquid separation, thereby avoiding the influence of water vapor and macromolecular hydrocarbons including butane, pentane, etc. on the adsorption capacity of the adsorption storage device for adsorbing low molecular alkanes such as methane and ethane. The associated gas recovery system provided by the present invention is used to carry out recovery experiments on 100% VOL methane and 100% VOL ethane at 4 MPa and 2 MPa respectively: the adsorption capacity for methane is 267-339 mL / g, the maximum temperature of the methane adsorption process is 47-65°C, and the adsorption temperature rise is 22-40°C; the adsorption capacity for ethane is 180-218 mL / g, the maximum temperature of the ethane adsorption process is 44-58°C, and the adsorption temperature rise is 19-33°C.In summary, in combination with the composition provided by the present invention, the adsorption storage device containing the composition, and the associated gas recovery system, a medium pressure-low temperature-phase change temperature control-adsorption storage single-pull well associated gas recovery process can be realized, which can effectively control the adsorption heat, and achieve low adsorption temperature rise (not higher than 50°C), high adsorption capacity (not less than 180mL / g), and low pressure (specifically 2-4MPa) for single-pull well associated gas with small gas volume, low casing pressure, and far away from the gathering and transportation station. High efficiency recovery is achieved at low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0117] Figure 1 is the nitrogen adsorption isotherm curve of the microporous MOFs material prepared in Example 1;

[0118] Figure 2 This is the HK (Original) pore size distribution diagram of the microporous MOFs material prepared in Example 1;

[0119] Figure 3 is the NLDFT pore size distribution diagram of the activated carbon used in the present invention;

[0120] Figure 4 is a nitrogen adsorption isotherm curve diagram of the multi-level porous MOFs material of Example 3;

[0121] Figure 5 This is the NLDFT pore size distribution diagram of the multi-level porous MOFs material of Example 3;

[0122] Figure 6 This is a penetration adsorption curve of ethane by the multi-level porous MOFs material of Example 3;

[0123] Figure 7 is the NLDFT pore size distribution diagram of the multi-level porous MOFs-based composite phase change material of Example 3;

[0124] Figure 8 is a penetration adsorption curve of ethane by the multi-level porous MOFs-based composite phase change material of Example 3;

[0125] Fig. 9 is a penetration adsorption curve of ethane by the multi-level porous MOFs-based composite phase change material of Example 4;

[0126] Fig.10 is a penetration adsorption curve of ethane by the multi-level porous MOFs-based composite phase change material of Example 5;

[0127] Fig.11Two filling methods of the first bed layer and the second bed layer in the adsorption storage device provided by the present invention are shown, wherein the first filling method is that in the adsorption storage tank, the first bed layer is a cylinder coaxial with the adsorption storage tank, and the second bed layer is a circular cylinder coaxial with the adsorption storage tank; in a cross section perpendicular to the axial direction of the adsorption storage tank, the second bed layer wraps the first bed layer in an annular shape; the second filling method is that in the adsorption storage tank, the first bed layer and the second bed layer are filled in sequence from the proximal end to the distal end of the adsorption storage tank inlet;

[0128] Fig.12 The associated gas recovery system provided by the present invention is shown;

[0129] Fig.13 is a methane adsorption curve diagram of Example 19;

[0130] Fig.14 is the ethane adsorption curve of Example 19;

[0131] Fig.15 is a methane adsorption curve diagram of Example 22;

[0132] Fig.16 This is the ethane adsorption curve of Example 22.

[0133] In this application, Fig.11 , Fig.12 The drawings are merely schematic, are only used to illustrate the principles of the present invention, and are not drawn according to actual scale. DETAILED DESCRIPTION

[0134] The present invention will be further described below in conjunction with examples, but the examples of the present invention are only exemplary descriptions, and the implementation methods do not constitute limitations of the present invention under any circumstances.

[0135] A first aspect of the present invention provides a multi-level porous MOFs-based composite phase change material, which includes a multi-level porous MOFs material having micropores, mesopores and macropores, and a phase change material loaded in the macropore channels of the multi-level porous MOFs material.

[0136] In the present invention, the multi-level porous MOFs-based composite phase change material comprises a multi-level porous MOFs material and a phase change material. The multi-level porous MOFs material has micropores, mesopores and macropores at the same time. The phase change material is loaded in the macropore channels of the multi-level porous MOFs material.

[0137] In the present invention, in order to make the hierarchical MOFs-based composite phase change material have better adsorption effect and self-temperature control characteristics, it is necessary to reasonably control the proportion of micropores, mesopores and macropores. In a preferred case, the ratio of the micropore volume, mesopore volume and macropore volume of the hierarchical MOFs material is 1-4:1-2:1, specifically 1:1:1, 2:1:1, 3:1:1, 4:1:1, 1:2:1, 2:2:1, 3:2:1 or 4:2:1.

[0138] Preferably, the specific surface area of ​​the multi-level porous MOFs material is 600-1700m 2 / g, specifically 600m 2 / g、700m 2 / g、800m 2 / g、900m 2 / g、1000m 2 / g、1100m 2 / g、1200m 2 / g、1300m 2 / g、1400m 2 / g、1500m 2 / g、1600m 2 / g or 1700m 2 / g.

[0139] In the present invention, in order to ensure that the phase change materials are loaded in the macropore channels of the multi-level porous MOFs-based composite phase change material, it is preferred that the phase change materials are all macromolecular phase change materials. Further preferably, the phase change materials are selected from one or more of polyols, fatty acids, straight-chain alkanes and paraffins.

[0140] Preferably, the polyols are polyethylene glycol and / or neopentyl glycol.

[0141] Preferably, the fatty acid is selected from one or more of lauric acid, stearic acid, palmitic acid and pentadecanoic acid.

[0142] Preferably, the straight-chain alkane is selected from one or more of n-tetradecane, n-hexadecane and n-octadecane.

[0143] In the present invention, when the phase change material contains paraffin, in order to ensure that the adsorption process can be controlled at a relatively low temperature, it is more appropriate to select paraffin with a phase change temperature of 30-50°C, and more preferably paraffin with a phase change temperature of 38°C.

[0144] The second aspect of the present invention provides a method for preparing the above-mentioned multi-level porous MOFs-based composite phase change material, the preparation method comprising the following steps:

[0145] (1) mixing a first metal salt with water to obtain a first metal salt solution;

[0146] (2) mixing a template, a first organic ligand and a first organic solvent to obtain a first organic phase solution;

[0147] (3) mixing the first metal salt solution with the first organic phase solution, and then performing a first reaction, separating the solid and the liquid after the reaction, and washing and activating the obtained solid in sequence to obtain a hierarchical MOFs material;

[0148] (4) Mixing the phase change material with a first organic solvent to obtain an organic phase change material solution, and immersing the multi-level porous MOFs material in the organic phase change material solution.

[0149] In the present invention, the first metal salt is selected from soluble metal salts and / or slightly soluble metal salts.

[0150] Preferably, the first metal salt is selected from aluminum chloride, aluminum chloride hexahydrate, aluminum nitrate, aluminum sulfate, aluminum acetate, ferric chloride, ferric chloride hexahydrate, ferric sulfate, ferric nitrate, ferric acetate, cupric chloride, cupric sulfate, cupric nitrate, cupric acetate, cupric acetate monohydrate, cupric sulfate pentahydrate, cupric nitrate trihydrate, chromium nitrate, chromium chloride, chromium sulfate, chromium acetate, chromium nitrate nonahydrate, chromium chloride hexahydrate, zirconium nitrate, zirconium chloride, zirconium sulfate, zirconium acetate, zirconium nitrate pentahydrate, One or more of zinc nitrate, zinc chloride, zinc sulfate, zinc acetate, zinc nitrate hexahydrate, zinc sulfate heptahydrate, nickel nitrate, nickel chloride, nickel sulfate, nickel acetate, nickel sulfate hexahydrate, nickel nitrate hexahydrate, nickel chloride hexahydrate, cobalt nitrate, cobalt chloride, cobalt sulfate, cobalt acetate, cobalt chloride hexahydrate, cobalt nitrate hexahydrate, cobalt sulfate monohydrate, manganese nitrate, manganese chloride, manganese sulfate, manganese acetate, manganese sulfate monohydrate, manganese nitrate hexahydrate, and manganese acetate dihydrate.

[0151] Preferably, the first metal salt is selected from one or more of aluminum chloride hexahydrate, copper acetate monohydrate, chromium nitrate nonahydrate, zinc nitrate hexahydrate, zirconium chloride and nickel chloride hexahydrate.

[0152] Preferably, in step (1), the content of the first metal salt in the first metal salt solution is 5-50 g / L, specifically 5 g / L, 10 g / L, 15 g / L, 20 g / L, 25 g / L, 30 g / L, 35 g / L, 40 g / L, 45 g / L or 50 g / L.

[0153] Preferably, the template is selected from one or more of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123), hexadecyltrimethylammonium bromide (CTAB), sodium dodecylbenzenesulfonate and N,N,N,N-tetramethylethylenediamine.

[0154] Preferably, the first organic ligand is selected from one or more of 2-methylterephthalic acid, 2-aminoterephthalic acid, 2-nitroterephthalic acid, 2-sulfonateterephthalic acid, 2,3-dihydroxyterephthalic acid, terephthalic acid, phthalic acid, trimesic acid, 2,5-thiophenedicarboxylic acid and triethylenediamine.

[0155] More preferably, the first organic ligand is selected from one or more of 2-aminoterephthalic acid, 2,5-thiophenedicarboxylic acid, trimesic acid, terephthalic acid and triethylenediamine.

[0156] Preferably, in step (2), the first organic solvent is selected from one or more of methanol, ethanol, N,N-dimethylformamide (DMF), dichloromethane and 1,2-dichloroethane.

[0157] Preferably, in step (2), the content of the template in the first organic phase solution is 10-80 g / L, and the content of the first organic ligand is 30-150 g / L.

[0158] In a specific embodiment, in step (2), the content of the template in the first organic phase solution can be 10 g / L, 20 g / L, 30 g / L, 40 g / L, 50 g / L, 60 g / L, 70 g / L or 80 g / L, and the content of the first organic ligand in the first organic phase solution can be 30 g / L, 40 g / L, 50 g / L, 60 g / L, 70 g / L, 80 g / L, 90 g / L, 100 g / L, 110 g / L, 120 g / L, 130 g / L, 140 g / L or 150 g / L.

[0159] In the preparation method described in the present invention, under preferred circumstances, the molar ratio of the amount of the first metal salt, the template and the first organic ligand is 1:0.03-1:1-2, wherein the first organic ligand is more than the first metal salt to ensure that after the multi-level porous MOFs material is generated, the unreacted first organic ligand can be washed away with the first organic solvent, and too much template will cause the quality of the multi-level porous MOFs material to be seriously reduced, so it is necessary to control the amount ratio of each raw material within the above range.

[0160] In a specific embodiment, the molar ratio of the first metal salt, the template and the first organic ligand can be 1:0.03:1, 1:0.04:1, 1:0.05:1, 1:0.06:1, 1:0.07:1, 1:0.08:1, 1:0.09:1, 1:1:1, 1:0.03:2, 1:0.04:2, 1:0.05:2, 1:0.06:2, 1:0.07:2, 1:0.08:2, 1:0.09:2 or 1:1:2.

[0161] In a preferred embodiment of the present invention, in step (3), the conditions of the first reaction include: temperature of 20-160° C. and time of 6-18 h.

[0162] Further preferably, in step (3), the conditions of the first reaction include: temperature of 40-110° C. and time of 8-16 h.

[0163] In a specific embodiment, in step (3), the temperature of the first reaction can be 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C or 110°C, and the time of the first reaction can be 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h or 16h.

[0164] In step (3) of the present invention, the obtained solid can be washed with a first organic solvent to remove unreacted first metal salt, template and first organic ligand, etc. The first organic solvent can be selected from one or more of methanol, ethanol, N,N-dimethylformamide, dichloromethane and 1,2-dichloroethane, preferably anhydrous ethanol is used for washing.

[0165] In step (3) of the present invention, there is no special requirement for the number of washings, and the unreacted first metal salt, template agent, first organic ligand, etc. can be removed.

[0166] In a preferred embodiment of the present invention, in step (3), the activation conditions include: temperature of 80-180° C., time of 1-24 h, and absolute vacuum of 20-80 kPa.

[0167] Further preferably, in step (3), the activation temperature is 100-160° C., and the activation time is 2-6 h.

[0168] In a specific embodiment, in step (3), the activation temperature can be 100°C, 110°C, 120°C, 130°C, 140°C, 150°C or 160°C, the activation time can be 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h or 6h, and the absolute vacuum degree of activation can be 20kPa, 25kPa, 30kPa, 35kPa, 40kPa, 45kPa, 50kPa, 55kPa, 60kPa, 65kPa, 70kPa, 75kPa or 80kPa.

[0169] Preferably, in step (4), the first organic solvent is selected from one or more of methanol, ethanol, N,N-dimethylformamide, dichloromethane and 1,2-dichloroethane, and is more preferably anhydrous ethanol.

[0170] In step (4) of the present invention, in order to ensure that the phase change materials are all loaded in the macropore channels of the multi-level porous MOFs-based composite phase change material, it is preferred that the phase change materials are all macromolecular phase change materials. Further preferably, the phase change materials are selected from one or more of polyols, fatty acids, straight-chain alkanes and paraffins.

[0171] Preferably, the polyols are polyethylene glycol and / or neopentyl glycol.

[0172] Preferably, the fatty acid is selected from one or more of lauric acid, stearic acid, palmitic acid and pentadecanoic acid.

[0173] Preferably, the straight-chain alkane is selected from one or more of n-tetradecane, n-hexadecane and n-octadecane.

[0174] In the present invention, when the phase change material contains paraffin, in order to ensure that the adsorption process can be controlled at a relatively low temperature, it is more appropriate to select paraffin with a phase change temperature of 30-50°C, and more preferably paraffin with a phase change temperature of 38°C.

[0175] In a preferred embodiment of the present invention, in step (4), the content of phase change material in the organic phase change material solution is 5-80 g / L.

[0176] In a specific embodiment, in step (4), the content of phase change material in the organic phase change material solution can be 5 g / L, 15 g / L, 25 g / L, 35 g / L, 45 g / L, 55 g / L, 65 g / L, 75 g / L or 80 g / L.

[0177] Preferably, in step (4), the weight ratio of the multi-level porous MOFs material to the organic phase change material is 1:0.05-0.5, specifically 1:0.05, 1:0.1, 1:0.15, 1:0.2, 1:0.25, 1:0.3, 1:0.35, 1:0.4, 1:0.45 or 1:0.5.

[0178] In a preferred embodiment of the present invention, in step (4), the immersion conditions include: a time of 4-7 hours and a temperature of 40-70°C.

[0179] In a specific embodiment, in step (4), the immersion time can be 4h, 4.5h, 5h, 5.5h, 6h, 6.5h or 7h, and the immersion temperature can be 40°C, 45°C, 50°C, 55°C, 60°C, 65°C or 70°C.

[0180] In step (4) of the present invention, after the impregnation is completed, filtration is required, and the solid obtained by filtration is dried.

[0181] In the present invention, by controlling the dosage ratio of the hierarchical porous MOFs material to the organic phase change material and the impregnation conditions, a suitable hierarchical porous MOFs-based composite phase change material can be obtained.

[0182] In the present invention, the drying conditions include: temperature of 60-70° C. and time of 4-6 hours.

[0183] In a specific embodiment, the drying temperature can be 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C or 70°C, and the drying time can be 4h, 4.5h, 5h, 5.5h or 6h.

[0184] The multi-level porous MOFs-based composite phase change material prepared by the above-mentioned preparation method in the present invention contains 5-30 weight % of phase change material. In a specific embodiment, the content of phase change material in the multi-level porous MOFs-based composite phase change material can be 5 weight %, 10 weight %, 15 weight %, 20 weight %, 25 weight % or 30 weight %.

[0185] A third aspect of the present invention provides an application of the above-mentioned multi-level porous MOFs-based composite phase change material in the adsorption of VOCs.

[0186] In the present invention, under the action of a suitable template, the self-assembly of the first metal salt and the first organic ligand is restricted, the original periodic network structure is destroyed, and the addition amount of the template and the reaction conditions are controlled at the same time, so as to obtain a multi-level porous MOFs material having micropore, mesopore and macropore structures at the same time. The multi-level porous MOFs material has the characteristics of three-dimensional ordered interconnected structure, adjustable pore size, ultra-large specific surface area, etc., and can be used as a carrier of phase change material. On the basis of the multi-level porous MOFs material, the phase change material is introduced into the macropore channel. Compared with the traditional MOFs material, in the process of micropore adsorption of VOCs, the mesopore channels in the multi-level pores contribute to the diffusion of the adsorbate, accelerate the mass transfer rate, and improve the adsorption rate, while the phase change material in the macropores offsets the adsorption heat effect through phase change, and can control the temperature rise of the bed, thereby significantly improving the adsorption efficiency of the bed. Therefore, the multi-level porous MOFs material loaded with the phase change material has the function of storing adsorption heat, which can effectively reduce the temperature rise of the bed during the adsorption of VOCs.

[0187] The multi-level porous MOFs-based composite phase change material provided by the present invention has the following advantages: (1) The present invention adopts the addition of a template to synthesize the multi-level porous MOFs material, and the porous coordination polymer is more evenly distributed and dense on the surface; (2) The synthesis method of the present invention is simple, avoiding cumbersome preparation processes and operating conditions, and is suitable for large-scale preparation and use. The synthesis of the multi-level porous material can be achieved by a one-step method, and the self-controlled temperature adsorption material can be obtained by a simple impregnation method, which has the prospect of large-scale production and application; (3) The multi-level porous MOFs-based composite phase change material prepared by the present invention uses the multi-level porous MOFs material as a matrix, has a high specific surface area and pore volume, has a certain number of micropores, mesopores and macropore structures, and fully develops the functions of pores of different sizes. In the process of microporous adsorption of VOCs, the mesopores are conducive to the mass transfer of the adsorbate and improve the adsorption rate, and the phase change material in the macropores can store adsorption heat to inhibit the temperature rise of the bed.

[0188] The multi-level porous MOFs-based composite phase change material of the present invention has the characteristics of high phase change material loading rate, low bed temperature rise and fast adsorption rate, and can be used in the field of VOCs control, especially for adsorbing light hydrocarbons, such as ethane, propane and other small molecules. It has broad application prospects in the adsorption control of VOCs and has achieved good technical effects.

[0189] In the following examples, copper acetate monohydrate, triethylenediamine, zinc nitrate hexahydrate and aluminum chloride hexahydrate are all products of Shanghai Aladdin Biochemical Technology Co., Ltd., chromium nitrate nonahydrate, zirconium chloride, nickel chloride hexahydrate, trimesic acid, 2,5-thiophenedicarboxylic acid and 2-aminoterephthalic acid are all products of Shanghai McLean Biochemical Technology Co., Ltd., CTAB is a product of Beijing Inokai Technology Co., Ltd., terephthalic acid is a product of Shanghai Kaishu Chemical Technology Co., Ltd., n-octadecane is a product of Tianjin Xiens Biochemical Technology Co., Ltd., 38°C and 45°C phase change paraffin is a product of Shanghai Ruentropy New Energy Technology Co., Ltd., anhydrous ethanol and DMF are products of China National Pharmaceutical Group Corporation, and activated carbon is a product of Calgon Carbon (Suzhou) Co., Ltd.

[0190] The room temperature below refers to 25℃.

[0191] Microporous MOFs (Metal Organic Frameworks) Materials

[0192] Preparation of microporous MOFs materials

[0193] Example 1

[0194] a. Add 2.8 g of a metal salt (copper acetate monohydrate) to a beaker containing water and perform ultrasound at room temperature to mix the mixture evenly to obtain a metal salt solution (the content of the metal salt is 35 g / L);

[0195] b. 3.8 g of the organic ligand (trimellitic acid) was added to a beaker containing an organic solvent (anhydrous ethanol), and ultrasonicated at room temperature to mix the mixture to obtain an organic phase solution (the content of the organic ligand was 32 g / L);

[0196] c. The metal salt solution obtained in step a and the organic phase solution obtained in step b are added to a reaction bottle (the molar ratio of the metal salt to the organic ligand is 1:1.29), placed in an oil bath, and reacted at 40°C for 8 hours. After the reaction, a suspension is obtained. After the suspension cools to room temperature, it is centrifuged and the obtained solid is washed twice with anhydrous ethanol. The washed solid is then placed in a vacuum oven and activated at 100°C and an absolute vacuum of 60 kPa for 6 hours to obtain a MOFs material, i.e., a microporous MOFs material.

[0197] Example 2

[0198] a. 3.1 g of a metal salt (aluminum chloride hexahydrate) was added to a beaker containing water and ultrasonically mixed at room temperature to obtain a metal salt solution (the content of the metal salt was 45 g / L);

[0199] b. 3.5 g of an organic ligand (2,5-thiophenedicarboxylic acid) was added to a beaker containing an organic solvent (DMF), and ultrasonicated at room temperature to mix the mixture to obtain an organic phase solution (the content of the organic ligand was 58 g / L);

[0200] c. The metal salt solution obtained in step a and the organic phase solution obtained in step b are added to a reaction bottle (the molar ratio of the amount of metal salt organic ligand is 1:1.58), placed in an oil bath, and reacted at 100°C for 9 hours. After the reaction, a suspension is obtained. After the suspension cools to room temperature, it is centrifuged and the obtained solid is washed twice with anhydrous ethanol. The washed solid is then placed in a vacuum oven and activated at 120°C and an absolute vacuum of 60 kPa for 4 hours to obtain a MOFs material, i.e., a microporous MOFs material.

[0201] Test Example 1

[0202] The nitrogen adsorption isotherms, specific surface areas, total pore volumes, micropore volumes, and pore sizes of the activated carbon used in the present invention and the microporous MOFs materials prepared in Examples 1 and 2 were measured. Here, the activated carbon used in the present invention and the microporous MOFs materials prepared in Example 1 are used as examples for detailed description.

[0203] Testing instrument: BSD-PM2 surface area analyzer produced by Beijing Best Instrument Technology Co., Ltd.

[0204] About 100 mg of the activated carbon powder sample and the microporous MOFs material powder sample prepared in Example 1 were weighed respectively, and after vacuum degassing treatment at 150° C. for 12 h, the corresponding data were obtained by testing at liquid nitrogen temperature (−196° C.) using nitrogen as a probe molecule.

[0205] The specific surface area (S) of the microporous MOFs material powder sample prepared in Example 1 was calculated according to the Brunauer-Emmet-Teller (BET) equation. BET ), the relative pressure point range is 0.01 to 0.15, and the correlation coefficient is required to be greater than 0.999, and the C value is greater than 0. The total pore volume of the microporous MOFs material powder sample prepared in Example 1 is obtained from the N2 adsorption amount when the relative pressure is 0.99. The pore size distribution range and micropore volume of the microporous MOFs material prepared in Example 1 are analyzed by the HK (Original) method: The specific surface area of ​​the microporous MOFs material prepared in Example 1 is 1500m 2 / g; it is a microporous material, and its nitrogen adsorption isotherm is as follows Figure 1 As shown; the pore size distribution is between 0.4 and 0.6nm (such as Figure 2As shown); the micropore volume (P / P0=0.123) of the HK (Original) method is about 0.56 mL / g, and the total pore volume (P / P0=0.99, pore diameter <195.6 nm) is 0.74 mL / g.

[0206] According to the same method, the microporous MOFs material prepared in Example 2 is also a microporous material with a specific surface area of ​​1000-1500m 2 / g, the total pore volume is in the range of 0.5-0.8mL / g, and the micropore volume is in the range of 0.4-0.7mL / g.

[0207] The specific surface area (S) of the activated carbon powder samples was calculated according to the Brunauer-Emmet-Teller (BET) equation. BET ), the relative pressure point range is 0.01 to 0.25, and the correlation coefficient is required to be greater than 0.999 and the C value is greater than 0. The total pore volume is obtained from the N2 adsorption at a relative pressure of 0.99. The pore size distribution range of activated carbon is calculated by the NLDFT method: the specific surface area of ​​activated carbon reaches 1000m 2 / g or more; it has both micropores and mesopores, and the pore size is mainly distributed between 0.5 and 4nm (such as Figure 3 As shown), the micropore volume (D≤2nm) by NLDFT method is about 0.38mL / g, and the total pore volume (D≤43nm) is about 0.64mL / g.

[0208] Preparation of hierarchical MOFs-based composite phase change materials

[0209] Example 3

[0210] (1) adding 2.8 g of metal salt (copper acetate monohydrate) into a beaker containing water, and performing ultrasonication at room temperature to mix the mixture evenly to obtain a metal salt solution (the content of the metal salt is 35 g / L);

[0211] (2) 3.1 g of the template (CTAB) and 3.8 g of the organic ligand (trimesic acid) were added to a beaker containing an organic solvent (anhydrous ethanol), and ultrasonicated at room temperature to mix them uniformly to obtain an organic phase solution (the content of the template was 26 g / L and the content of the organic ligand was 32 g / L);

[0212] (3) The metal salt solution obtained in step (1) and the organic phase solution obtained in step (2) are added to a reaction bottle (the molar ratio of the metal salt, the template and the organic ligand is 1:0.61:1.29), placed in an oil bath, and reacted at 40°C for 8 hours. After the reaction, a suspension is obtained. After the suspension cools to room temperature, it is centrifuged and the obtained solid is washed twice with anhydrous ethanol. The washed solid is then placed in a vacuum oven and activated at 100°C and an absolute vacuum of 40 kPa for 6 hours to obtain a multi-level porous MOFs material B1;

[0213] (4) Add 0.6 g of phase change material (paraffin with a phase change temperature of 38°C) to an organic solvent (anhydrous ethanol), heat and stir at 60°C until completely dissolved to obtain an organic phase change material solution (the content of the phase change material is 60 g / L), place 1.5 g of the multi-level porous MOFs material obtained in step (3) in the organic phase change material solution (the weight ratio of the multi-level porous MOFs material to the organic phase change material is 1:0.4), immerse at 40°C for 5 h, and then filter, and dry the obtained solid at 60°C for 4 h to obtain a multi-level porous MOFs-based composite phase change material A1.

[0214] Example 4

[0215] (1) 3.1 g of metal salt (aluminum chloride hexahydrate) was added to a beaker containing water, and ultrasonicated at room temperature to mix the mixture evenly to obtain a metal salt solution (the content of the metal salt was 45 g / L);

[0216] (2) 3.6 g of template (CTAB) and 3.5 g of organic ligand (2,5-thiophenedicarboxylic acid) were added to a beaker containing an organic solvent (DMF), and ultrasonicated at room temperature to mix them uniformly to obtain an organic phase solution (the content of the template was 60 g / L and the content of the organic ligand was 58 g / L);

[0217] (3) adding the metal salt solution obtained in step (1) and the organic phase solution obtained in step (2) into a reaction bottle (the molar ratio of the metal salt, template and organic ligand is 1:0.77:1.58), placing the reaction bottle in an oil bath, reacting at 100° C. for 9 h, obtaining a suspension after the reaction, and centrifuging the suspension after cooling to room temperature. The obtained solid was washed twice with anhydrous ethanol, and then the washed solid was placed in a vacuum oven and activated at 120° C. and an absolute vacuum of 40 kPa for 4 h to obtain a hierarchical MOFs material;

[0218] (4) Add 0.6 g of phase change material (paraffin with a phase change temperature of 38°C) to an organic solvent (anhydrous ethanol), heat and stir at 60°C until completely dissolved to obtain an organic phase change material solution (the content of the phase change material is 60 g / L), place 2 g of the multi-level porous MOFs material obtained in step (3) in the organic phase change material solution (the weight ratio of the multi-level porous MOFs material to the organic phase change material is 1:0.3), immerse at 70°C for 5 h, and then filter, and dry the obtained solid at 60°C for 4 h to obtain a multi-level porous MOFs-based composite phase change material A2.

[0219] Example 5

[0220] (1) adding 4 g of metal salt (chromium nitrate nonahydrate) into a beaker containing water, and performing ultrasonication at room temperature to mix the mixture evenly to obtain a metal salt solution (the content of the metal salt is 44 g / L);

[0221] (2) adding 2.6 g of template (CTAB) and 3.4 g of organic ligand (2-aminoterephthalic acid) into a beaker containing an organic solvent (anhydrous ethanol), and performing ultrasonication at room temperature to mix them uniformly to obtain an organic phase solution (the content of template is 50 g / L, and the content of organic ligand is 65 g / L);

[0222] (3) The metal salt solution obtained in step (1) and the organic phase solution obtained in step (2) are transferred into a reaction kettle (the molar ratio of the metal salt, the template and the organic ligand is 1:0.71:1.88), placed in an oven, and reacted at 90° C. for 12 h. After the reaction, a suspension is obtained. After the suspension cools to room temperature, it is centrifuged and the obtained solid is washed twice with anhydrous ethanol. The washed solid is then placed in a vacuum oven and activated at 120° C. and an absolute vacuum of 60 kPa for 4 h to obtain a multi-level porous MOFs material;

[0223] (4) Add 0.5 g of phase change material (paraffin with a phase change temperature of 38°C) to an organic solvent (anhydrous ethanol), heat and stir at 60°C until completely dissolved to obtain an organic phase change material solution (the content of the phase change material is 50 g / L), place 1.5 g of the multi-level porous MOFs material obtained in step (3) in the organic phase change material solution (the weight ratio of the multi-level porous MOFs material to the organic phase change material is 1:0.33), immerse at 60°C for 5 h, and then filter, and dry the obtained solid at 60°C for 4 h to obtain a multi-level porous MOFs-based composite phase change material A3.

[0224] Example 6

[0225] (1) adding 2.5 g of metal salt (zinc nitrate hexahydrate) into a beaker containing water, and performing ultrasonication at room temperature to mix the mixture evenly to obtain a metal salt solution (the content of the metal salt is 30 g / L);

[0226] (2) 2.6 g of template (CTAB) and 1.9 g of organic ligand (terephthalic acid) were added to a beaker containing an organic solvent (DMF), and ultrasonicated at room temperature to mix them uniformly to obtain an organic phase solution (the content of the template was 60 g / L and the content of the organic ligand was 44 g / L);

[0227] (3) The metal salt solution obtained in step (1) and the organic phase solution obtained in step (2) are transferred into a reaction kettle (the molar ratio of the metal salt, the template and the organic ligand is 1:0.84:1.36), placed in an oven, and reacted at 110° C. for 13 h. After the reaction is completed, a suspension is obtained. After the suspension cools to room temperature, it is centrifuged and the obtained solid is washed twice with anhydrous ethanol. The washed solid is then placed in a vacuum oven and activated at 140° C. and an absolute vacuum of 60 kPa for 6 h to obtain a multi-level porous MOFs material;

[0228] (4) Add 0.5 g of phase change material (paraffin with a phase change temperature of 38°C) to an organic solvent (anhydrous ethanol), heat and stir at 60°C until completely dissolved to obtain an organic phase change material solution (the content of the phase change material is 50 g / L), place 2 g of the multi-level porous MOFs material obtained in step (3) in the organic phase change material solution (the weight ratio of the multi-level porous MOFs material to the organic phase change material is 1:0.25), immerse at 50°C for 5 h, and then filter, and dry the obtained solid at 60°C for 4 h to obtain a multi-level porous MOFs-based composite phase change material A4.

[0229] Example 7

[0230] (1) adding 1.2 g of metal salt (zirconium chloride) into a beaker containing water, and performing ultrasonication at room temperature to mix the mixture evenly to obtain a metal salt solution (the content of the metal salt is 35 g / L);

[0231] (2) 1.6 g of template (CTAB) and 1.1 g of organic ligand (terephthalic acid) were added to a beaker containing an organic solvent (DMF), and ultrasonicated at room temperature to mix them uniformly to obtain an organic phase solution (the content of template was 70 g / L and the content of organic ligand was 48 g / L);

[0232] (3) The metal salt solution obtained in step (1) and the organic phase solution obtained in step (2) are transferred into a reaction kettle (the molar ratio of the metal salt, the template and the organic ligand is 1:0.85:1.29), placed in an oven, and reacted at 90° C. for 12 h. After the reaction, a suspension is obtained. After the suspension cools to room temperature, it is centrifuged and the obtained solid is washed twice with anhydrous ethanol. The washed solid is then placed in a vacuum oven and activated for 4 h at 120° C. and an absolute vacuum of 60 kPa to obtain a multi-level porous MOFs material;

[0233] (4) Add 0.3 g of phase change material (paraffin with a phase change temperature of 38°C) to an organic solvent (anhydrous ethanol), heat and stir at 60°C until completely dissolved to obtain an organic phase change material solution (the content of the phase change material is 37.5 g / L), place 3 g of the multi-level porous MOFs material obtained in step (3) in the organic phase change material solution (the weight ratio of the multi-level porous MOFs material to the organic phase change material is 1:0.1), immerse at 40°C for 5 h, and then filter, and dry the obtained solid at 60°C for 4 h to obtain a multi-level porous MOFs-based composite phase change material A5.

[0234] Example 8

[0235] (1) adding 0.6 g of metal salt (nickel chloride hexahydrate) into a beaker containing water, and performing ultrasonication at room temperature to mix the mixture evenly to obtain a metal salt solution (the content of the metal salt is 35 g / L);

[0236] (2) adding 0.8 g of template (CTAB) and 0.6 g of organic ligand (0.4 g of terephthalic acid and 0.2 g of triethylenediamine) into a beaker containing an organic solvent (DMF), and performing ultrasonication at room temperature to mix them uniformly to obtain an organic phase solution (the content of the template is 50 g / L, and the content of the organic ligand is 38 g / L);

[0237] (3) The metal salt solution obtained in step (1) and the organic phase solution obtained in step (2) are transferred into a reaction kettle (the molar ratio of the metal salt, the template and the organic ligand is 1:0.86:1.66), placed in an oven, and reacted at 110° C. for 16 hours. After the reaction is completed, a suspension is obtained. After the suspension cools to room temperature, it is centrifuged and the obtained solid is washed twice with anhydrous ethanol. The washed solid is then placed in a vacuum oven and activated at 120° C. and an absolute vacuum of 60 kPa for 4 hours to obtain a multi-level porous MOFs material;

[0238] (4) Add 0.2 g of phase change material (paraffin with a phase change temperature of 38°C) to an organic solvent (anhydrous ethanol), heat and stir at 60°C until completely dissolved to obtain an organic phase change material solution (the content of the phase change material is 40 g / L), place 2 g of the multi-level porous MOFs material obtained in step (3) in the organic phase change material solution (the weight ratio of the multi-level porous MOFs material to the organic phase change material is 1:0.1), immerse at 50°C for 5 h, and then filter, and dry the obtained solid at 60°C for 4 h to obtain a multi-level porous MOFs-based composite phase change material A6.

[0239] Example 9

[0240] The method of Example 3 was implemented, except that the phase change material used was n-octadecane, to obtain a multi-level porous MOFs-based composite phase change material A7.

[0241] Example 10

[0242] The method of Example 4 was followed, except that the phase change material used was n-octadecane, to obtain a multi-level porous MOFs-based composite phase change material A8.

[0243] Embodiment 11

[0244] The method of Example 5 was followed, except that the phase change material used was n-octadecane, to obtain a multi-level porous MOFs-based composite phase change material A9.

[0245] Example 12

[0246] The method of Example 3 was followed, except that the phase change material used was paraffin with a phase change temperature of 45° C., to obtain a multi-level porous MOFs-based composite phase change material A10.

[0247] Embodiment 13

[0248] The method of Example 4 was followed, except that the phase change material used was paraffin with a phase change temperature of 45° C., to obtain a multi-level porous MOFs-based composite phase change material A11.

[0249] Comparative Example 1

[0250] 0.6 g of phase change material (paraffin with a phase change temperature of 38°C) was added to an organic solvent (anhydrous ethanol), heated and stirred at 60°C until completely dissolved to obtain an organic phase change material solution (the content of phase change material was 60 g / L), 1.5 g of the MOFs material prepared in Example 1 (herein numbered D1-1) was placed in the organic phase change material solution (the weight ratio of the MOFs material to the organic phase change material was 1:0.4), immersed at 40°C for 5 h, and then filtered, and the obtained solid was dried at 60°C for 4 h to obtain MOFs-based composite phase change material D1-2.

[0251] Comparative Example 2

[0252] 0.6 g of phase change material (n-octadecane) was added to an organic solvent (anhydrous ethanol), heated and stirred at 60°C until completely dissolved to obtain an organic phase change material solution (the content of phase change material was 60 g / L), 2 g of the MOFs material prepared in Example 2 was placed in the organic phase change material solution (the weight ratio of the MOFs material to the organic phase change material was 1:0.3), immersed at 70°C for 5 h, and then filtered, and the obtained solid was dried at 60°C for 4 h to obtain the MOFs-based composite phase change material D2.

[0253] Test Example 2

[0254] The specific surface area, total pore volume, pore size, maximum temperature of the adsorption process, ethane adsorption amount and breakthrough point adsorption rate of A1-A11, B1, D1-1, D1-2 and D2 were measured respectively.

[0255] Testing instrument: BSD-PM2 surface area analyzer produced by Beijing Best Instrument Technology Co., Ltd.

[0256] About 100 mg of powder samples were weighed respectively, and after vacuum degassing at 150°C for 12 h, the corresponding data were obtained by testing with nitrogen as the probe molecule at liquid nitrogen temperature (-196°C);

[0257] Among them, the specific surface area (S BET ) was calculated using the Brunauer-Emmet-Teller (BET) equation, with a relative pressure point range of 0.01 to 0.15, and a correlation coefficient greater than 0.999 and a C value greater than 0. The total pore volume was obtained from the N2 adsorption at a relative pressure of 0.99. The pore size distribution was obtained using the nonlocalized density functional theory (NLDFT) method;

[0258] The multi-component adsorption breakthrough curve analyzer (BSD-MAB) of Best Instrument Technology (Beijing) Co., Ltd. was used to measure the breakthrough adsorption curve of ethane gas for each sample, and the adsorption amount of ethane was calculated; the highest temperature during the adsorption process was measured by the temperature sensor on the analyzer;

[0259] The specific operation process of measuring the penetration curve of ethane gas is as follows: first, weigh about 150g of sample and load it into the penetration column, purge it with helium at a flow rate of 300ml / min for 2h to remove the impurity gas on the surface of the sample. Place the penetration column in a 298K constant temperature water bath, and after the test environment is stable, start the penetration experiment, test the ethane penetration adsorption curve (gas flow rate is 900mL / min, ethane concentration is 10%VOL, test temperature and pressure are 25℃ and 5bar respectively), and calculate the adsorption amount;

[0260] The adsorption amount of each component was calculated by the following formula:

[0261]

[0262] Note: This calculation formula takes into account the concentration change caused by the real-time change of the outlet flow rate due to adsorption, which improves the accuracy of calculating the adsorption amount by concentration integral.

[0263] Q n吸附 : The amount of adsorbent adsorbed on adsorbate n (unit: mL)

[0264] Q n入总 : The total flow rate of adsorbate n flowing into the column within the time ΔT (unit: mL)

[0265] Q n出总 : The total flow rate of adsorbate n flowing out of the column within the time ΔT (unit: mL)

[0266] q 总入 : Total gas flow rate through the column inlet (unit: mL / min)

[0267] q 载气 : Carrier gas flow rate (unit: mL / min)

[0268] C n0 : The percentage concentration of adsorbate n at the entrance of the penetration column (%)

[0269] C nt : The percentage concentration of adsorbate n at a certain moment at the outlet of the penetration column (%)

[0270] ΔT: total time from the start to the end of adsorption (unit: s) for the adsorption amount of each component.

[0271] The calculation formula of penetration point adsorption rate is:

[0272]

[0273] Q: The amount of adsorbate n when the adsorbent is penetrated (unit: mL / g)

[0274] t: time when the adsorbent is penetrated (unit: min)

[0275] The results are shown in Table 1 and Figure 4-10 As shown ( Figure 4 is the nitrogen adsorption isotherm of B1; Figure 5 is the pore size distribution range of B1, Figure 6 This is the breakthrough adsorption curve of B1 for ethane. Figure 7 is the pore size distribution range of A1, Figure 8 is the breakthrough adsorption curve of A1 for ethane, Fig. 9 is the breakthrough adsorption curve of A2 for ethane, Fig.10 (a) is the breakthrough adsorption curve of A3 for ethane.

[0276] Table 1. Specific surface area, total pore volume, maximum adsorption temperature, ethane adsorption amount and breakthrough point adsorption rate of A1-A11, B1, D1-1, D1-2 and D2

[0277]

[0278] Figure 4 and Figure 5 The nitrogen adsorption isotherm and pore size distribution of B1 are given. It can be seen from the figure that a multi-level porous MOFs material is generated under the action of the template. Figure 5 It can be seen that B1 has micropores, mesopores and macropores at the same time, and the ratio of micropore volume, mesopore volume and macropore volume is 1.76:1.28:1. Table 1 shows the pore structure data, adsorption temperature rise and adsorption capacity of the composite material. Since the phase change material occupies a certain pore volume, the pore volume of A1 is smaller than that of B1 and D1-1. During the ethane adsorption process, the material phase changes and absorbs adsorption heat, so the temperature rise of A1 is the lowest. The lower temperature is conducive to the material adsorbing ethane, so the ethane adsorption capacity of A1 is higher than that of B1 and D1-1.

[0279] Examples 3-8 illustrate that the present method forms a porous MOFs material under the action of a template and can be composited with a phase change material to form a self-controlled temperature adsorption material, and the pore volume of the obtained material is 0.3-0.5 mL / g, and the ethane adsorption capacity is 63-74 mL / g, wherein the temperature rise caused by the adsorption of ethane is 13-16° C. Materials A7 and A8 illustrate that the composite material with the addition of n-octadecane can suppress the adsorption temperature rise through the phase change process, but it has a certain impact on the pore structure of the adsorption material.

[0280] Compared with Example 3 and Comparative Example 1, material A1 is a composite of multi-level porous MOFs and phase change materials, while material D1-2 is a microporous structure, and it is difficult for the phase change material to enter the micropores. Therefore, there are significant differences in the temperature control effect and adsorption performance of the two materials. Since it is difficult for the phase change material to enter the micropores, the structures and performances of D1-1 and D1-2 are basically similar; similarly, it is also difficult for the phase change material in Comparative Example 2 to enter the micropores, so D2 does not have the function of phase change temperature control, and the ethane adsorption capacity of D2 is relatively low.

[0281] Composition, adsorption storage device and associated gas recovery system

[0282] The multi-level porous MOFs-based composite phase change materials or activated carbon or microporous MOFs materials used in Examples 14-17 and Comparative Examples 3-5 are:

[0283] Activated carbon: specific surface area, total pore volume, micropore volume, and pore diameter are as shown in Test Example 1.

[0284] Microporous MOFs material: The MOFs material prepared in Example 1, its specific surface area, total pore volume, micropore volume, and pore diameter are as shown in Test Example 1.

[0285] Multi-level porous MOFs-based composite phase change material: The multi-level porous MOFs-based composite phase change material A1 prepared in Example 3, its specific surface area, total pore volume, pore size, maximum temperature of the adsorption process, ethane adsorption amount and penetration point adsorption rate are shown in Table 1 in Test Example 2.

[0286] It should be noted that: in actual use, the capacity specification of the adsorption storage tank used can be determined according to the content of low molecular weight hydrocarbons such as methane and ethane in the target associated gas, and the total filling mass of the first bed and the second bed in the adsorption storage tank can be further determined.

[0287] Embodiment 14

[0288] The composition provided in this embodiment:

[0289] Composition A in this embodiment: a hierarchical MOFs-based composite phase change material and activated carbon in a mass ratio of 4:3;

[0290] Composition B in this embodiment: a hierarchical porous MOFs-based composite phase change material and a microporous MOFs material in a mass ratio of 2:6.

[0291] The adsorption storage device provided in this embodiment:

[0292] First bed: composition A;

[0293] Second bed layer: composition B;

[0294] Adsorption storage tank: 50L adsorption tank;

[0295] The filling mass ratio and total filling amount of the first bed layer and the second bed layer: the first bed layer and the second bed layer are filled with a total of 15.6 kg in a mass ratio of 2:5;

[0296] Bed filling method in adsorption storage tank: In the adsorption storage tank, Fig.11 In the filling method 1 shown, the first bed layer is a cylinder coaxial with the adsorption storage tank, and the second bed layer is a circular cylinder coaxial with the adsorption storage tank; in the cross section perpendicular to the axis of the adsorption storage tank, the second bed layer wraps the first bed layer in an annular shape to obtain an adsorption storage device.

[0297] The associated gas recovery system provided in this embodiment:

[0298] like Fig.12 As shown, the adsorption storage unit adopts the adsorption storage device provided in this embodiment, and the adsorption tank 11 is filled with activated carbon.

[0299] Embodiment 15

[0300] The composition provided in this embodiment:

[0301] Composition C in this embodiment: a hierarchical MOFs-based composite phase change material and activated carbon in a mass ratio of 3:1;

[0302] Composition D in this embodiment: a hierarchical porous MOFs-based composite phase change material and a microporous MOFs material in a mass ratio of 3:1.

[0303] The adsorption storage device provided in this embodiment:

[0304] First bed: composition C;

[0305] Second bed: composition D;

[0306] Adsorption storage tank: 50L adsorption tank;

[0307] The filling mass ratio and total filling amount of the first bed layer and the second bed layer: the first bed layer and the second bed layer are filled with a total of 14.6 kg in a mass ratio of 3:2;

[0308] Bed filling method in adsorption storage tank: In the adsorption storage tank, Fig.11 In the filling method 1 shown, the first bed layer is a cylinder coaxial with the adsorption storage tank, and the second bed layer is a circular cylinder coaxial with the adsorption storage tank; in the cross section perpendicular to the axis of the adsorption storage tank, the second bed layer wraps the first bed layer in an annular shape to obtain an adsorption storage device.

[0309] The associated gas recovery system provided in this embodiment:

[0310] like Fig.12As shown, the adsorption storage unit adopts the adsorption storage device provided in this embodiment, and the adsorption tank 11 is filled with activated carbon.

[0311] Example 16

[0312] The composition provided in this embodiment:

[0313] Composition E in this embodiment: a multi-level porous MOFs-based composite phase change material and activated carbon in a mass ratio of 2:6;

[0314] The composition F in this embodiment includes a hierarchical porous MOFs-based composite phase change material and a microporous MOFs material in a mass ratio of 4:3.

[0315] The adsorption storage device provided in this embodiment:

[0316] First bed: composition E;

[0317] Second bed: composition F;

[0318] Adsorption storage tank: 50L adsorption tank;

[0319] The filling mass ratio and total filling amount of the first bed layer and the second bed layer: the first bed layer and the second bed layer are filled with a total of 17kg in a mass ratio of 3:2;

[0320] Bed filling method in adsorption storage tank: In the adsorption storage tank, Fig.11 In the filling method 1 shown, the first bed layer is a cylinder coaxial with the adsorption storage tank, and the second bed layer is a circular cylinder coaxial with the adsorption storage tank; in the cross section perpendicular to the axis of the adsorption storage tank, the second bed layer wraps the first bed layer in an annular shape to obtain an adsorption storage device.

[0321] The associated gas recovery system provided in this embodiment:

[0322] like Fig.12 As shown, the adsorption storage unit adopts the adsorption storage device provided in this embodiment, and the adsorption tank 11 is filled with activated carbon.

[0323] Embodiment 17

[0324] The composition provided in this embodiment:

[0325] Composition G in this embodiment: a multi-level porous MOFs-based composite phase change material and activated carbon in a mass ratio of 4:3;

[0326] The composition H in this embodiment includes a multi-level porous MOFs-based composite phase change material and a microporous MOFs material in a mass ratio of 2:6;

[0327] The adsorption storage device provided in this embodiment:

[0328] First bed: composition G;

[0329] Second bed: composition H;

[0330] Adsorption storage tank: 50L adsorption tank;

[0331] The filling mass ratio and total filling amount of the first bed layer and the second bed layer: the first bed layer and the second bed layer are filled with a total of 14kg in a mass ratio of 2:5;

[0332] Bed filling method in adsorption storage tank: In the adsorption storage tank, Fig.11 The second filling method shown is to fill the first bed layer and the second bed layer in sequence from the proximal end to the distal end of the adsorption storage tank inlet to obtain an adsorption storage device.

[0333] The associated gas recovery system provided in this embodiment:

[0334] like Fig.12 As shown, the adsorption storage unit adopts the adsorption storage device provided in this embodiment, and the adsorption tank 11 is filled with activated carbon.

[0335] Comparative Example 3

[0336] The adsorption storage device provided in this comparative example:

[0337] Adsorption storage tank: 50L adsorption tank;

[0338] Bed filling method in adsorption storage tank: In the adsorption storage tank, no Fig.11 Using filling methods 1 and 2, 16.4 kg of multi-level porous MOFs-based composite phase change material is directly filled to obtain an adsorption storage device.

[0339] The associated gas recovery system provided in this comparative example:

[0340] like Fig.12 As shown, the adsorption storage unit adopts the adsorption storage device provided in this comparative example, and the adsorption tank 11 is filled with activated carbon.

[0341] Comparative Example 4

[0342] The adsorption storage device provided in this comparative example:

[0343] Adsorption storage tank: 50L adsorption tank;

[0344] Bed filling method in adsorption storage tank: In the adsorption storage tank, no Fig.11 In the filling methods 1 and 2, 15.2 kg of activated carbon is directly filled to obtain an adsorption storage device.

[0345] The associated gas recovery system provided in this comparative example:

[0346] like Fig.12 As shown, the adsorption storage unit adopts the adsorption storage device provided in this comparative example, and the adsorption tank 11 is filled with activated carbon.

[0347] Comparative Example 5

[0348] The adsorption storage device provided in this comparative example:

[0349] Adsorption storage tank: 50L adsorption tank;

[0350] Bed filling method in adsorption storage tank: In the adsorption storage tank, no Fig.11 Using filling methods 1 and 2, 13.6 kg of microporous MOFs material was directly filled to obtain an adsorption storage device.

[0351] The associated gas recovery system provided in this comparative example:

[0352] like Fig.12 As shown, the adsorption storage unit adopts the adsorption storage device provided in this comparative example, and the adsorption tank 11 is filled with activated carbon.

[0353] Utilize the associated gas recovery system provided in any one of Examples 14 to 17 and recover the associated gas of a single well in accordance with the associated gas recovery process provided in the present invention. Here, the process of recovering the associated gas of a single well by using the associated gas recovery system provided in Example 14 and implementing the associated gas recovery process provided in the present invention is described in detail as an example.

[0354] Embodiment 18

[0355] The associated gas in the single well in this embodiment is a small gas volume (less than 500m 3 / d), associated gas with a high proportion of low molecular weight alkanes (methane + ethane content exceeding 90% VOL) ​​and a certain humidity (15% RH to 100% RH).

[0356] Step 1) The associated gas from the single-pull well enters the buffer tank 2 through the inlet valve 1, and the buffer tank is used to adjust the pressure fluctuation of the system to maintain the stability of the system operating conditions; then the associated gas from the single-pull well passes through the buffer tank to the compressor 3 with a set pressure of 4MPa, and the associated gas from the single-pull well is pressurized to 4MPa (absolute pressure) in cooperation with the compression heat exchanger 4. At this time, the temperature of the pressurized associated gas from the single-pull well is also increased to 70°C, and the water vapor and some macromolecular hydrocarbons including butane and pentane therein are converted from gas to liquid due to the increase in pressure. The obtained compressed gas and compressed condensate are separated into a gas and liquid in the gas-liquid separation tank 5 connected to the compressor; in this way, part of the water vapor and macromolecular hydrocarbons in the associated gas from the single-pull well are removed, which is beneficial to reduce the influence of water vapor and macromolecular hydrocarbons on the adsorption capacity of low-molecular alkanes such as methane and ethane in the adsorption storage device in the subsequent adsorption storage unit;

[0357] Step 2) When the pressure in the compressor 3 reaches its set value, open valve 6 to allow the compressed gas to enter the heat exchanger 7 with a set pressure of 4MPa. At this point, valve 13 is always in a closed state; as the compressed gas fills and the pressure in the heat exchanger 7 reaches its set value, adjust the opening of valve 13 to maintain the pressure in the heat exchanger at about 4MPa; the compressed gas exchanges heat with the refrigerant of the heat exchanger and the temperature drops to about 2°C. During the cooling process, most of the water vapor and a small amount of large molecular hydrocarbons including butane and pentane in the compressed gas are liquefied to obtain condensed liquid, while low molecular alkanes such as methane and ethane are converted into dry cooling gas. The obtained condensed liquid flows through the condensate discharge pipeline 19 connected to the heat exchanger and enters the condensate tank 9 through valve 8 (in which the condensed liquid achieves preliminary oil-water separation) , so far the secondary gas-liquid separation is completed; in the secondary gas-liquid separation process, a small amount of dry cooling gas will enter the condensate tank along with the condensed liquid. In addition, the pressure drop in the condensate tank will also cause a small amount of butane and pentane in the condensed liquid to be converted from liquid to gas again to produce volatile gas; the dry cooling gas and the volatile gas enter the adsorption tank 11 filled with activated carbon through the valve 10, wherein the volatile gas is adsorbed and removed by the adsorption tank 11 to avoid entering the associated gas recovery system again, and the dry cooling gas flows through the pressure relief pipeline 18 and the pressure relief valve 12 into the buffer tank, and the single-pull well associated gas that continuously enters the buffer tank at the inlet valve 1 continues to enter the system for recovery, so that the influence of water vapor and macromolecular hydrocarbons including butane, pentane, etc. on the adsorption capacity of the adsorption storage device can be further reduced on the basis of step 1);

[0358] Step 3) The dry cooling gas obtained by the cooling and condensing unit treatment enters the adsorption storage device 16 through the valve 14 and the manual valve 15 for adsorption storage, and the pressure of the adsorption storage device 16 is set to 4MPa. When the pressure therein reaches the set value, it is switched to the parallel adsorption storage device through the valve 14; in addition, the pressure of the pressure-limiting valve 17 of each adsorption storage device is set to 6MPa. When the pressure in the adsorption storage device is higher than the set pressure of the pressure-limiting valve 17, the pressure-limiting valve 17 opens to automatically discharge, so as to avoid the danger caused by excessive internal pressure due to the increase in temperature in the adsorption storage device. When the adsorption storage device reaches its set pressure, close the manual valve 15, collect the gas to the transfer station regularly (for example, every day), and release the gas in the adsorption storage device by desorption from the device: first open the manual valve 15 for natural pressure relief, and control the opening of the manual valve 15 to allow the desorbed gas to slowly enter the recovery system of the transfer station to avoid excessive impact on the system; then perform vacuum desorption, turn on the vacuum pump to pump the adsorption storage device, and reduce the relative pressure in the device to -90kPa. After maintaining for 30 minutes, close the manual valve 15 and the desorption is completed; the adsorption storage device after desorption is transported back to the associated gas recovery system to continue the adsorption storage of dry cooling gas.

[0359] Recovering methane and ethane using associated gas recovery systems and associated gas recovery processes

[0360] In order to facilitate indoor experimental evaluation, the capacity specifications of the adsorption storage devices in the associated gas recovery systems provided in Examples 14-17 and Comparative Examples 3-5 used for recovering methane and ethane in Examples 19-22 and Comparative Examples 6-8 were adjusted to laboratory level (specifically, they were all adjusted to 250mL adsorption tanks, and the total filling amount of the bed in the adsorption storage tanks was reduced to 2 weight % of the original total filling amount); in addition, a temperature detector (such as a PT110 temperature detector) was set in the above-mentioned adjusted 250mL adsorption tank, and the maximum temperature of the adsorption storage device during the methane and ethane adsorption process was measured during the recovery of methane and ethane in Examples 19-22 and Comparative Examples 6-8.

[0361] The adsorption capacity of methane and ethane in the process of recovering methane and ethane in Examples 19-22 and Comparative Examples 6-8 is obtained by dividing the total amount of methane or ethane gas flowing through the inlet valve 1 of the associated gas recovery system by the total mass of the bed filled in the adsorption storage tank. The specific calculation formula is as follows:

[0362]

[0363] Among them, Q n : The adsorption amount of adsorbent n recovered by the associated gas recovery system, in mL / g;

[0364] q n : Flow rate of adsorbate n, in mL / min;

[0365] t: The time required for the adsorption storage tank to reach the set pressure, in min;

[0366] m: The total mass of the bed filled in the adsorption storage tank, in g.

[0367] Embodiment 19

[0368] Methane is recovered using the associated gas recovery system provided in Example 14:

[0369] 100% VOL methane enters the buffer tank 2 through the inlet valve 1 at a flow rate of 1200 mL / min. The buffer tank is used to adjust the pressure fluctuation of the system to maintain the stability of the system operating conditions; then the methane gas passes through the buffer tank to the compressor 3 with a set pressure of 4 MPa, and cooperates with the compression heat exchanger 4 to increase the pressure of the methane gas to 4 MPa (absolute pressure). At this time, the temperature of the pressurized methane gas also rises to about 70°C. When the pressure in the compressor reaches the set value (i.e. 4 MPa), the valve 6 is opened to allow the compressed methane gas to enter the heat exchanger 7 with a set pressure of 4 MPa. At this point, valve 13 is always in a closed state; as the compressed methane gas fills up and makes the pressure in the heat exchanger 7 reach the set value (i.e. 4MPa), the opening of valve 13 is adjusted to keep the pressure in the heat exchanger at about 4MPa; the compressed methane gas is cooled down to about 2°C after heat exchange with the refrigerant of the heat exchanger and is converted into cooled and dry methane gas, which enters the adsorption storage device 16 through valve 14 and manual valve 15 for adsorption storage. After 22 minutes, the adsorption storage device 16 reaches its set pressure of 4MPa, and valve 14 and manual valve 15 are cut off.

[0370] During the methane adsorption process, the adsorption curve of the adsorption storage device for methane and the maximum temperature of the bed in the adsorption storage device during the adsorption process were measured. The specific results are shown in Fig.13 , Table 2.

[0371] Ethane is recovered using the associated gas recovery system provided in Example 14:

[0372] 100%VOL ethane enters the buffer tank 2 through the inlet valve 1 at a flow rate of 1200mL / min. The buffer tank is used to adjust the pressure fluctuation of the system to maintain the stability of the system operating conditions; then the ethane gas passes through the buffer tank to the compressor 3 with a set pressure of 2MPa, and cooperates with the compression heat exchanger 4 to increase the pressure of the ethane gas to 2MPa (absolute pressure). At this time, the temperature of the pressurized ethane gas also rises to about 40℃. When the pressure in the compressor reaches the set value (i.e. 2MPa), the valve 6 is opened to allow the compressed ethane gas to enter the heat exchanger 7 with a set pressure of 2MPa. , so far the valve 13 is always in a closed state; as the compressed ethane gas fills up and makes the pressure in the heat exchanger 7 reach the set value (i.e. 2MPa), the opening of the valve 13 is adjusted to keep the pressure in the heat exchanger at about 2MPa; the compressed ethane gas is cooled down to about 2°C after heat exchange with the refrigerant of the heat exchanger and is converted into cooled and dried ethane gas, which enters the adsorption storage device 16 through the valve 14 and the manual valve 15 for adsorption storage. After 14.2 minutes, the adsorption storage device 16 reaches its set pressure of 2MPa, and the valve 14 and the manual valve 15 are cut off.

[0373] During the ethane adsorption process, the adsorption capacity of the adsorption storage device for ethane and the maximum temperature of the bed in the adsorption storage device during the adsorption process were determined. The specific results are shown in Fig.14 , Table 2.

[0374] Embodiment 20

[0375] Methane is recovered using the associated gas recovery system provided in Example 15:

[0376] 100% VOL methane enters the buffer tank 2 through the inlet valve 1 at a flow rate of 1200 mL / min. The buffer tank is used to adjust the pressure fluctuation of the system to maintain the stability of the system operating conditions; then the methane gas passes through the buffer tank to the compressor 3 with a set pressure of 4 MPa, and cooperates with the compression heat exchanger 4 to increase the pressure of the methane gas to 4 MPa (absolute pressure). At this time, the temperature of the pressurized methane gas also rises to about 70°C. When the pressure in the compressor reaches the set value (i.e. 4 MPa), the valve 6 is opened to allow the compressed methane gas to enter the heat exchanger 7 with a set pressure of 4 MPa. , so far the valve 13 is always in a closed state; as the compressed methane gas fills up and makes the pressure in the heat exchanger 7 reach the set value (i.e. 4MPa), the opening of the valve 13 is adjusted to keep the pressure in the heat exchanger at about 4MPa; the compressed methane gas is cooled down to about 2°C after heat exchange with the refrigerant of the heat exchanger and is converted into cooled and dry methane gas, which enters the adsorption storage device 16 through the valve 14 and the manual valve 15 for adsorption storage. After 16.6 minutes, the adsorption storage device 16 reaches its set pressure of 4MPa, and the valve 14 and the manual valve 15 are cut off.

[0377] During the methane adsorption process, the adsorption capacity of the adsorption storage device for methane and the maximum temperature of the bed in the adsorption storage device during the adsorption process were measured. The specific results are shown in Table 2.

[0378] Ethane is recovered using the associated gas recovery system provided in Example 15:

[0379] 100%VOL ethane enters the buffer tank 2 through the inlet valve 1 at a flow rate of 1200mL / min. The buffer tank is used to adjust the pressure fluctuation of the system to maintain the stability of the system operating conditions; then the ethane gas passes through the buffer tank to the compressor 3 with a set pressure of 2MPa, and cooperates with the compression heat exchanger 4 to increase the pressure of the ethane gas to 2MPa (absolute pressure). At this time, the temperature of the pressurized ethane gas also rises to about 40℃. When the pressure in the compressor reaches the set value (i.e. 2MPa), the valve 6 is opened to allow the compressed ethane gas to enter the heat exchanger 7 with a set pressure of 2MPa. , so far the valve 13 is always in a closed state; as the compressed ethane gas fills up and makes the pressure in the heat exchanger 7 reach the set value (i.e. 2MPa), the opening of the valve 13 is adjusted to keep the pressure in the heat exchanger at about 2MPa; the compressed ethane gas is cooled down to about 2°C after heat exchange with the refrigerant of the heat exchanger and is converted into cooled and dried ethane gas, which enters the adsorption storage device 16 through the valve 14 and the manual valve 15 for adsorption storage. After 11.2 minutes, the adsorption storage device 16 reaches its set pressure of 2MPa, and the valve 14 and the manual valve 15 are cut off.

[0380] During the ethane adsorption process, the adsorption capacity of the adsorption storage device for ethane and the maximum temperature of the bed in the adsorption storage device during the adsorption process were measured. The specific results are shown in Table 2.

[0381] Embodiment 21

[0382] Methane is recovered using the associated gas recovery system provided in Example 16:

[0383] 100% VOL methane enters the buffer tank 2 through the inlet valve 1 at a flow rate of 1200 mL / min. The buffer tank is used to adjust the pressure fluctuation of the system to maintain the stability of the system operating conditions; then the methane gas passes through the buffer tank to the compressor 3 with a set pressure of 4 MPa, and cooperates with the compression heat exchanger 4 to increase the pressure of the methane gas to 4 MPa (absolute pressure). At this time, the temperature of the pressurized methane gas also rises to about 70°C. When the pressure in the compressor reaches the set value (i.e. 4 MPa), the valve 6 is opened to allow the compressed methane gas to enter the heat exchanger 7 with a set pressure of 4 MPa. , so far the valve 13 is always in a closed state; as the compressed methane gas fills up and makes the pressure in the heat exchanger 7 reach the set value (i.e. 4MPa), the opening of the valve 13 is adjusted to keep the pressure in the heat exchanger at about 4MPa; the compressed methane gas is cooled down to about 2°C after heat exchange with the refrigerant of the heat exchanger and is converted into cooled and dried methane gas, which enters the adsorption storage device 16 through the valve 14 and the manual valve 15 for adsorption storage. After 22.1 minutes, the adsorption storage device 16 reaches its set pressure of 4MPa, and the valve 14 and the manual valve 15 are cut off.

[0384] During the methane adsorption process, the adsorption capacity of the adsorption storage device for methane and the maximum temperature of the bed in the adsorption storage device during the adsorption process were measured. The specific results are shown in Table 2.

[0385] Ethane is recovered using the associated gas recovery system provided in Example 16:

[0386] 100%VOL ethane enters the buffer tank 2 through the inlet valve 1 at a flow rate of 1200mL / min. The buffer tank is used to adjust the pressure fluctuation of the system to maintain the stability of the system operating conditions; then the ethane gas passes through the buffer tank to the compressor 3 with a set pressure of 2MPa, and cooperates with the compression heat exchanger 4 to increase the pressure of the ethane gas to 2MPa (absolute pressure). At this time, the temperature of the pressurized ethane gas also rises to about 40℃. When the pressure in the compressor reaches the set value (i.e. 2MPa), the valve 6 is opened to allow the compressed ethane gas to enter the heat exchanger 7 with a set pressure of 2MPa. , so far the valve 13 is always in a closed state; as the compressed ethane gas fills up and makes the pressure in the heat exchanger 7 reach the set value (i.e. 2MPa), the opening of the valve 13 is adjusted to keep the pressure in the heat exchanger at about 2MPa; the compressed ethane gas is cooled down to about 2°C after heat exchange with the refrigerant of the heat exchanger and is converted into cooled and dried ethane gas, which enters the adsorption storage device 16 through the valve 14 and the manual valve 15 for adsorption storage. After 13.6 minutes, the adsorption storage device 16 reaches its set pressure of 2MPa, and the valve 14 and the manual valve 15 are cut off.

[0387] During the ethane adsorption process, the adsorption capacity of the adsorption storage device for ethane and the maximum temperature of the bed in the adsorption storage device during the adsorption process were measured. The specific results are shown in Table 2.

[0388] Embodiment 22

[0389] Methane is recovered using the associated gas recovery system provided in Example 17:

[0390] 100% VOL methane enters the buffer tank 2 through the inlet valve 1 at a flow rate of 1200 mL / min. The buffer tank is used to adjust the pressure fluctuation of the system to maintain the stability of the system operating conditions; then the methane gas passes through the buffer tank to the compressor 3 with a set pressure of 4 MPa, and cooperates with the compression heat exchanger 4 to increase the pressure of the methane gas to 4 MPa (absolute pressure). At this time, the temperature of the pressurized methane gas also rises to about 70°C. When the pressure in the compressor reaches the set value (i.e. 4 MPa), the valve 6 is opened to allow the compressed methane gas to enter the heat exchanger 7 with a set pressure of 4 MPa. , so far the valve 13 is always in a closed state; as the compressed methane gas fills up and makes the pressure in the heat exchanger 7 reach the set value (i.e. 4MPa), the opening of the valve 13 is adjusted to keep the pressure in the heat exchanger at about 4MPa; the compressed methane gas is cooled down to about 2°C after heat exchange with the refrigerant of the heat exchanger and is converted into cooled and dry methane gas, which enters the adsorption storage device 16 through the valve 14 and the manual valve 15 for adsorption storage. After 15.6 minutes, the adsorption storage device 16 reaches its set pressure of 4MPa, and the valve 14 and the manual valve 15 are cut off.

[0391] During the methane adsorption process, the adsorption capacity of the adsorption storage device for methane and the maximum temperature of the bed in the adsorption storage device during the adsorption process were determined. The specific results are shown in Fig.15 , Table 2.

[0392] Ethane is recovered using the associated gas recovery system provided in Example 17:

[0393] 100%VOL ethane enters the buffer tank 2 through the inlet valve 1 at a flow rate of 1200mL / min. The buffer tank is used to adjust the pressure fluctuation of the system to maintain the stability of the system operating conditions; then the ethane gas passes through the buffer tank to the compressor 3 with a set pressure of 2MPa, and cooperates with the compression heat exchanger 4 to increase the pressure of the ethane gas to 2MPa (absolute pressure). At this time, the temperature of the pressurized ethane gas also rises to about 40℃. When the pressure in the compressor reaches the set value (i.e. 2MPa), the valve 6 is opened to allow the compressed ethane gas to enter the heat exchanger 7 with a set pressure of 2MPa. , so far the valve 13 is always in a closed state; as the compressed ethane gas fills up and makes the pressure in the heat exchanger 7 reach the set value (i.e. 2MPa), the opening of the valve 13 is adjusted to keep the pressure in the heat exchanger at about 2MPa; the compressed ethane gas is cooled down to about 2°C after heat exchange with the refrigerant of the heat exchanger and is converted into cooled and dried ethane gas, which enters the adsorption storage device 16 through the valve 14 and the manual valve 15 for adsorption storage. After 14.2 minutes, the adsorption storage device 16 reaches its set pressure of 2MPa, and the valve 14 and the manual valve 15 are cut off.

[0394] During the ethane adsorption process, the adsorption capacity of the adsorption storage device for ethane and the maximum temperature of the bed in the adsorption storage device during the adsorption process were determined. The specific results are shown in Fig.16 , Table 2.

[0395] Comparative Example 6

[0396] Methane is recovered using the associated gas recovery system provided in Comparative Example 3:

[0397] 100% VOL methane enters the buffer tank 2 through the inlet valve 1 at a flow rate of 1200 mL / min. The buffer tank is used to adjust the pressure fluctuation of the system to maintain the stability of the system operating conditions; then the methane gas passes through the buffer tank to the compressor 3 with a set pressure of 4 MPa, and cooperates with the compression heat exchanger 4 to increase the pressure of the methane gas to 4 MPa (absolute pressure). At this time, the temperature of the pressurized methane gas also rises to about 70°C. When the pressure in the compressor reaches the set value (i.e. 4 MPa), the valve 6 is opened to allow the compressed methane gas to enter the heat exchanger 7 with a set pressure of 4 MPa. , so far the valve 13 is always in a closed state; as the compressed methane gas fills up and makes the pressure in the heat exchanger 7 reach the set value (i.e. 4MPa), the opening of the valve 13 is adjusted to keep the pressure in the heat exchanger at about 4MPa; the compressed methane gas is cooled down to about 2°C after heat exchange with the refrigerant of the heat exchanger and is converted into cooled and dry methane gas, which enters the adsorption storage device 16 through the valve 14 and the manual valve 15 for adsorption storage. After 12.9 minutes, the adsorption storage device 16 reaches its set pressure of 4MPa, and the valve 14 and the manual valve 15 are cut off.

[0398] During the methane adsorption process, the adsorption capacity of the adsorption storage device for methane and the maximum temperature of the bed in the adsorption storage device during the adsorption process were measured. The specific results are shown in Table 2.

[0399] Ethane is recovered using the associated gas recovery system provided in Comparative Example 3:

[0400] 100%VOL ethane enters the buffer tank 2 through the inlet valve 1 at a flow rate of 1200mL / min. The buffer tank is used to adjust the pressure fluctuation of the system to maintain the stability of the system operating conditions; then the ethane gas passes through the buffer tank to the compressor 3 with a set pressure of 2MPa, and cooperates with the compression heat exchanger 4 to increase the pressure of the ethane gas to 2MPa (absolute pressure). At this time, the temperature of the pressurized ethane gas also rises to about 40℃. When the pressure in the compressor reaches the set value (i.e. 2MPa), the valve 6 is opened to allow the compressed ethane gas to enter the heat exchanger 7 with a set pressure of 2MPa. At this point, valve 13 is always in a closed state; as the compressed ethane gas fills up and makes the pressure in the heat exchanger 7 reach the set value (i.e. 2MPa), the opening of valve 13 is adjusted to keep the pressure in the heat exchanger at about 2MPa; the compressed ethane gas is cooled down to about 2°C after heat exchange with the refrigerant of the heat exchanger and is converted into cooled and dried ethane gas, which enters the adsorption storage device 16 through valve 14 and manual valve 15 for adsorption storage. After 9.7 minutes, the adsorption storage device 16 reaches its set pressure of 2MPa, and valve 14 and manual valve 15 are cut off.

[0401] During the ethane adsorption process, the adsorption capacity of the adsorption storage device for ethane and the maximum temperature of the bed in the adsorption storage device during the adsorption process were measured. The specific results are shown in Table 2.

[0402] Comparative Example 7

[0403] Methane is recovered using the associated gas recovery system provided in Comparative Example 4:

[0404] 100% VOL methane enters the buffer tank 2 through the inlet valve 1 at a flow rate of 1200 mL / min. The buffer tank is used to adjust the pressure fluctuation of the system to maintain the stability of the system operating conditions; then the methane gas passes through the buffer tank to the compressor 3 with a set pressure of 4 MPa, and cooperates with the compression heat exchanger 4 to increase the pressure of the methane gas to 4 MPa (absolute pressure). At this time, the temperature of the pressurized methane gas also rises to about 70°C. When the pressure in the compressor reaches the set value (i.e. 4 MPa), the valve 6 is opened to allow the compressed methane gas to enter the heat exchanger 7 with a set pressure of 4 MPa. , so far the valve 13 is always in a closed state; as the compressed methane gas fills up and makes the pressure in the heat exchanger 7 reach the set value (i.e. 4MPa), the opening of the valve 13 is adjusted to keep the pressure in the heat exchanger at about 4MPa; the compressed methane gas is cooled down to about 2°C after heat exchange with the refrigerant of the heat exchanger and is converted into cooled and dry methane gas, which enters the adsorption storage device 16 through the valve 14 and the manual valve 15 for adsorption storage. After 10.7 minutes, the adsorption storage device 16 reaches its set pressure of 4MPa, and the valve 14 and the manual valve 15 are cut off.

[0405] During the methane adsorption process, the adsorption capacity of the adsorption storage device for methane and the maximum temperature of the bed in the adsorption storage device during the adsorption process were measured. The specific results are shown in Table 2.

[0406] Ethane is recovered using the associated gas recovery system provided in Comparative Example 4:

[0407] 100%VOL ethane enters the buffer tank 2 through the inlet valve 1 at a flow rate of 1200mL / min. The buffer tank is used to adjust the pressure fluctuation of the system to maintain the stability of the system operating conditions; then the ethane gas passes through the buffer tank to the compressor 3 with a set pressure of 2MPa, and cooperates with the compression heat exchanger 4 to increase the pressure of the ethane gas to 2MPa (absolute pressure). At this time, the temperature of the pressurized ethane gas also rises to about 40℃. When the pressure in the compressor reaches the set value (i.e. 2MPa), the valve 6 is opened to allow the compressed ethane gas to enter the heat exchanger 7 with a set pressure of 2MPa. At this point, valve 13 is always in a closed state; as the compressed ethane gas fills up and makes the pressure in the heat exchanger 7 reach the set value (i.e. 2MPa), the opening of valve 13 is adjusted to keep the pressure in the heat exchanger at about 2MPa; the compressed ethane gas is cooled down to about 2°C after heat exchange with the refrigerant of the heat exchanger and is converted into cooled and dried ethane gas, which enters the adsorption storage device 16 through valve 14 and manual valve 15 for adsorption storage. After 8.8 minutes, the adsorption storage device 16 reaches its set pressure of 2MPa, and valve 14 and manual valve 15 are cut off.

[0408] During the ethane adsorption process, the adsorption capacity of the adsorption storage device for ethane and the maximum temperature of the bed in the adsorption storage device during the adsorption process were measured. The specific results are shown in Table 2.

[0409] Comparative Example 8

[0410] Methane is recovered using the associated gas recovery system provided in Comparative Example 5:

[0411] 100% VOL methane enters the buffer tank 2 through the inlet valve 1 at a flow rate of 1200 mL / min. The buffer tank is used to adjust the pressure fluctuation of the system to maintain the stability of the system operating conditions; then the methane gas passes through the buffer tank to the compressor 3 with a set pressure of 4 MPa, and cooperates with the compression heat exchanger 4 to increase the pressure of the methane gas to 4 MPa (absolute pressure). At this time, the temperature of the pressurized methane gas also rises to about 70°C. When the pressure in the compressor reaches the set value (i.e. 4 MPa), the valve 6 is opened to allow the compressed methane gas to enter the heat exchanger 7 with a set pressure of 4 MPa. , so far the valve 13 is always in a closed state; as the compressed methane gas fills up and makes the pressure in the heat exchanger 7 reach the set value (i.e. 4MPa), the opening of the valve 13 is adjusted to keep the pressure in the heat exchanger at about 4MPa; the compressed methane gas is cooled down to about 2°C after heat exchange with the refrigerant of the heat exchanger and is converted into cooled and dry methane gas, which enters the adsorption storage device 16 through the valve 14 and the manual valve 15 for adsorption storage. After 13.2 minutes, the adsorption storage device 16 reaches its set pressure of 4MPa, and the valve 14 and the manual valve 15 are cut off.

[0412] During the methane adsorption process, the adsorption capacity of the adsorption storage device for methane and the maximum temperature of the bed in the adsorption storage device during the adsorption process were measured. The specific results are shown in Table 2.

[0413] Ethane is recovered using the associated gas recovery system provided in Comparative Example 5:

[0414] 100%VOL ethane enters the buffer tank 2 through the inlet valve 1 at a flow rate of 1200mL / min. The buffer tank is used to adjust the pressure fluctuation of the system to maintain the stability of the system operating conditions; then the ethane gas passes through the buffer tank to the compressor 3 with a set pressure of 2MPa, and cooperates with the compression heat exchanger 4 to increase the pressure of the ethane gas to 2MPa (absolute pressure). At this time, the temperature of the pressurized ethane gas also rises to about 40℃. When the pressure in the compressor reaches the set value (i.e. 2MPa), the valve 6 is opened to allow the compressed ethane gas to enter the heat exchanger 7 with a set pressure of 2MPa. At this point, valve 13 is always in a closed state; as the compressed ethane gas fills up and makes the pressure in the heat exchanger 7 reach the set value (i.e. 2MPa), the opening of valve 13 is adjusted to keep the pressure in the heat exchanger at about 2MPa; the compressed ethane gas is cooled down to about 2°C after heat exchange with the refrigerant of the heat exchanger and is converted into cooled and dried ethane gas, which enters the adsorption storage device 16 through valve 14 and manual valve 15 for adsorption storage. After 9.2 minutes, the adsorption storage device 16 reaches its set pressure of 2MPa, and valve 14 and manual valve 15 are cut off.

[0415] During the ethane adsorption process, the adsorption capacity of the adsorption storage device for ethane and the maximum temperature of the bed in the adsorption storage device during the adsorption process were measured. The specific results are shown in Table 2.

[0416] Evaluation of methane and ethane adsorption results

[0417] Fig.13 , 15 The methane adsorption curves of Examples 19 and 22 are shown in sequence; Fig.14 , 16 The adsorption curves of ethane in Examples 19 and 22 are shown in Table 2. The adsorption capacities of methane and ethane in Examples 19-22 and Comparative Examples 6-8, as well as the maximum bed temperatures during the adsorption of methane and ethane are shown in Table 2.

[0418] Table 2. Adsorption capacity of methane and ethane and the maximum bed temperature of the adsorption storage device during the adsorption process

[0419]

[0420] Combination Figures 13 to 16From the data in Table 2, it can be seen that Examples 19 to 22 sequentially use the associated gas recovery systems provided by Examples 14 to 17 (wherein the adsorption storage devices are all filled with the composition) for methane and ethane adsorption effects and temperature control effects during the adsorption process. The adsorption capacity for methane is 267-339 mL / g, and the maximum temperature of the adsorption storage device during the methane adsorption process is 47-65°C, and the corresponding adsorption temperature rise is 22-40°C; the adsorption capacity for ethane is 180-218 mL / g, and the maximum temperature of the adsorption storage device during the ethane adsorption process is 44-58°C, and the corresponding adsorption temperature rise is 19-33°C. Comparative Examples 6, 7, and 8 use the associated gas recovery systems provided in Comparative Examples 3, 4, and 5 in turn (the adsorption and storage devices therein are respectively filled with only multi-level pore MOFs-based composite phase change materials, activated carbon, and microporous MOFs materials), and cannot simultaneously achieve higher methane and ethane adsorption capacities and better temperature control effects during the adsorption process: Comparative Example 6 uses the associated gas recovery system provided in Comparative Example 3 (the adsorption and storage devices therein are only filled with multi-level pore MOFs-based composite phase change materials), and has a better temperature control effect during the adsorption of methane and ethane, with the highest temperatures being only 41°C and 39°C, respectively, and the corresponding adsorption temperature rises being 16°C and 14°C, respectively, but its adsorption capacities for methane and ethane are significantly lower, specifically 189 mL / g and 142 mL / g, respectively; Comparative Example 7 uses the associated gas recovery system provided in Comparative Example 3 (the adsorption and storage devices therein are only filled with multi-level pore MOFs-based composite phase change materials), and has a better temperature control effect during the adsorption of methane and ethane, with the highest temperatures being only 41°C and 39°C, respectively, and the corresponding adsorption temperature rises being 16°C and 14°C, respectively. However, its adsorption capacities for methane and ethane are significantly lower, specifically 189 mL / g and 142 mL / g, respectively; The associated gas recovery system provided in Comparative Example 4 (in which the adsorption storage device is only filled with activated carbon) has the worst temperature control effect during the adsorption of methane and ethane, with the highest temperatures reaching 71°C and 69°C, respectively, and the corresponding adsorption temperature rises of 46°C and 44°C. In addition, its adsorption capacity for methane and ethane is also relatively low, with the adsorption capacities of 169mL / g and 139mL / g, respectively. Comparative Example 8 uses the associated gas recovery system provided in Comparative Example 5 (in which the adsorption storage device is only filled with microporous MOFs material). The temperature control effect during the adsorption of methane and ethane is poor, with the highest temperatures of 67°C and 64°C, respectively, and the corresponding adsorption temperature rises of 42°C and 39°C. Its adsorption capacity for methane and ethane is relatively low, with the adsorption capacities of 233mL / g and 162mL / g, respectively. The above data show that in the composition filled in the adsorption storage device provided by the present invention, the multi-level pore MOFs-based composite phase change material and activated carbon, the multi-level pore MOFs-based composite phase change material and microporous MOFs material, and the multi-level pore MOFs-based composite phase change material, activated carbon and microporous MOFs have synergistic effects in reducing the adsorption temperature rise and improving the adsorption capacity for low-molecular alkanes such as methane and ethane, thereby reducing the temperature rise of the bed in the adsorption storage device during the adsorption process, achieving control of the adsorption heat, and improving the adsorption capacity of low-molecular alkanes such as methane and ethane, and being able to effectively recover the associated gas of a single-pull well with a small gas volume, low casing gas pressure, and a long distance from a gathering and transportation station.

[0421] Although the present invention has been described with reference to specific embodiments, it will be appreciated by those skilled in the art that various changes may be made without departing from the true spirit and scope of the present invention. In addition, the subject matter, spirit and scope of the present invention may be varied to accommodate specific situations, materials, material combinations and methods. All of these changes are included within the scope of the claims of the present invention.

Claims

1. A composition comprising a multi-level porous MOFs-based composite phase change material and an adsorption material.

2. The composition according to claim 1, characterized in that The multi-level porous MOFs-based composite phase change material includes a multi-level porous MOFs material having micropores, mesopores and macropores, and a phase change material loaded in the macropore channels of the multi-level porous MOFs material; and / or The adsorption material is activated carbon or microporous MOFs material.

3. The composition according to claim 1 or 2, characterized in that The mass ratio of the multi-level porous MOFs-based composite phase change material to the adsorption material is 2-4:1-6.

4. The composition according to claim 2, characterized in that The ratio of the micropore volume, mesopore volume and macropore volume of the hierarchical MOFs material is 1-4:1-2:1; and / or The phase change material is selected from one or more of polyols, fatty acids, linear alkanes and paraffins; Preferably, the specific surface area of ​​the multi-level porous MOFs material is 600-1700m 2 / g; Preferably, the polyols are polyethylene glycol and / or neopentyl glycol; Preferably, the fatty acid is selected from one or more of lauric acid, stearic acid, palmitic acid and pentadecanoic acid; Preferably, the straight-chain alkane is selected from one or more of n-tetradecane, n-hexadecane and n-octadecane.

5. The composition according to any one of claims 1 to 4, characterized in that The adsorption material is activated carbon; Preferably, the specific surface area of ​​the activated carbon is 1000-1600m 2 / g; and / or The total pore volume of the activated carbon is 0.4-1.0 mL / g; and / or the micropore volume in the total pore volume is 0.2-0.7 mL / g.

6. The composition according to any one of claims 1 to 4, characterized in that The adsorption material is a microporous MOFs material; Preferably, the specific surface area of ​​the microporous MOFs material is 1000-1500m 2 / g; and / or The total pore volume of the microporous MOFs material is 0.5-0.8 mL / g; and / or the micropore volume in the total pore volume is 0.4-0.7 mL / g.

7. An adsorption storage device, comprising an adsorption storage tank and a first bed layer and a second bed layer filled in the adsorption storage tank; The first bed layer is the composition according to claim 5; The second bed layer is the composition according to claim 6.

8. The adsorption storage device according to claim 7, characterized in that: The mass ratio of the first bed layer to the second bed layer is 1-3:2-7; Preferably, the mass ratio of the first bed layer to the second bed layer is 2-3:2-5.

9. The adsorption storage device according to claim 7 or 8, characterized in that: In the adsorption storage tank, the first bed layer and the second bed layer are sequentially filled from the proximal end to the distal end of the adsorption storage tank inlet.

10. The adsorption storage device according to claim 7 or 8, characterized in that: In the adsorption storage tank, the first bed layer is a cylinder coaxial with the adsorption storage tank, and the second bed layer is a circular cylinder coaxial with the adsorption storage tank; Preferably, in a cross section perpendicular to the axial direction of the adsorption storage tank, the second bed layer wraps the first bed layer in an annular shape.

11. An associated gas recovery system, comprising a pressurizing unit, a cooling, condensing and dehumidifying unit and an adsorption storage unit connected in sequence; The boosting unit comprises a compressor (3) and a gas-liquid separation tank (5) connected to the compressor, wherein: The compressor is used to pressurize the associated gas to produce compressed condensate and compressed gas, and the gas-liquid separation tank is used to perform a gas-liquid separation on the compressed condensate and compressed gas; The cooling, condensing and dehumidifying unit comprises a heat exchanger (7), a condensate discharge pipeline (19) and a condensate tank (9) connected in sequence, wherein the heat exchanger is used to cool, condense and dehumidify the compressed gas to produce dry cooling gas and condensed liquid; the condensate discharge pipeline and the condensate tank are used to perform secondary gas-liquid separation on the dry cooling gas and the condensed liquid; The adsorption storage unit comprises an adsorption storage device (16) for adsorption storage of the dry cooling gas; The adsorption storage device is the adsorption storage device according to any one of claims 7 to 10.

12. An associated gas recovery process comprising the following steps: Providing an associated gas recovery system according to claim 11; 1) The associated gas enters the compressor (3) to be compressed and heated to obtain the compressed gas and compressed condensate, and the compressed condensate enters the gas-liquid separation tank (5) to achieve the primary gas-liquid separation; 2) passing the compressed gas obtained in step 1) into the heat exchanger (7) for cooling, condensation and dehumidification to obtain the dry cooling gas and condensed liquid, and the condensed liquid is discharged into the condensate tank (9) via the condensate discharge pipeline (19) to achieve the secondary gas-liquid separation; 3) The dry cooling gas obtained in step 2) is introduced into the adsorption storage device (16) for adsorption storage.

13. The associated gas recovery process according to claim 12, characterized in that: In step 1), the pressure of the compressed gas is 2-4 MPa and / or the temperature is 40-70° C.; and / or In step 2), the temperature of the dry cooling gas is 0-5°C.

14. Use of any one of the composition according to any one of claims 1 to 6, the adsorption storage device according to any one of claims 7 to 10, the associated gas recovery system according to claim 11, and the associated gas recovery process according to claim 12 or 13 in single-pull well associated gas recovery.

Citation Information

Patent Citations

  • Oil field gas recovering (mixed hydrocarbon recovering, liquefied natural gas recovering) process technology

    CN102559236A

  • Mixture of an adsorbent and a phase change material with an adapted density

    CN103442785A

  • Recovery process for oil-associated gases

    CN109233927A

  • Ethephon production tail gas treatment device

    CN216878584U

  • Method for storing gaseous hydrocarbons

    WO2009071436A1

Cited By

  • ANG natural gas adsorption tank assembly

    PL451660A1

  • Systems and methods for gas storage

    US12480622B2

  • Systems and methods for gas storage

    US20240191840A1